Polypropylene-based resin composition and method for producing the same, and film
The polypropylene resin composition, combining specific linear and branched polypropylene resins, addresses the challenge of achieving high melting point, strength, and tearability, while ensuring low temperature heat sealing and reduced weight.
Patent Information
- Application Number
- JP2023149974
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Existing polypropylene resin compositions struggle to achieve a balance between high melting point, strength, and tearability, while also maintaining low temperature heat sealing and reducing weight.
A polypropylene resin composition comprising a specific linear polypropylene resin (Y) and a branched polypropylene resin (X) with defined properties, including a melt flow rate, melting point, and flow activation energy, which are combined in a specific ratio to produce a non-stretched film with enhanced properties.
The composition achieves a high melting point match strength and excellent tearability, while maintaining the required properties for low temperature heat sealing and reducing weight, thus addressing the limitations of existing technologies.
Smart Images

Figure 2025042823000009 
Figure 2025042823000010 
Figure 2025042823000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a polypropylene resin composition, a method for producing the same, and a film. [Background technology]
[0002] In recent years, there has been a demand for thinner films from the perspectives of cost reduction (e.g., reducing raw material costs, improving productivity through high-speed film production, reducing weight, and environmental issues. However, excessive thinning leads to a decrease in the stiffness, or strength, of the film. In addition, for films that require heat sealability, materials with low melting points are required as raw materials. The melting point of polypropylene resins can be lowered by copolymerizing comonomers such as ethylene and butene, but this also leads to a decrease in strength. A decrease in strength not only adversely affects transportability and unwinding from a roll during film processing, but also reduces the inherent functions of the final package, such as protecting the contents and maintaining the shape.
[0003] In order to solve the problem of strength reduction, the strength of the film can be increased. Methods for increasing strength include adding a nucleating agent, which is a crystallization promoter (e.g., Patent Documents 1, 2, and 5), adding an ethylene-based polymer having a specific density and a specific MFR (e.g., Patent Document 3), and adding a resin-reinforcing filler such as talc, carbon nanofiber, or cellulose nanofiber. However, when inorganic nucleating agents are added, they become foreign bodies and cause defects in the appearance of the film called fish eyes, and when organic network nucleating agents are added, there is a concern that the low molecular weight components derived from the nucleating agents will contaminate the contents of the package. In addition, when ethylene polymers are added, there is a concern that the film strength will decrease and the fish eyes will worsen due to gelation of polyethylene. In addition, when resin reinforced fillers are added, not only will there be significant changes in the texture, feel, and optical properties, but the specific gravity will also increase, making them unsuitable for the purpose of reducing weight.
[0004] Other methods for increasing strength include adjusting the film-forming conditions, such as promoting oriented crystallization by lowering the extrusion temperature or promoting crystal growth by increasing the cooling and solidifying temperature (for example, Patent Document 4). However, there are problems such as deterioration in the thickness accuracy of the obtained film and changes in the optical properties.
[0005] Furthermore, as a method for increasing strength, the addition of a specific branched polypropylene resin is mentioned (for example, Patent Document 6). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-3364 [Patent Document 2] Japanese Patent Application Publication No. 9-118776 [Patent Document 3] JP 2008-127487 A [Patent Document 4] JP 2011-236357 A [Patent Document 5] JP 2016-11380 A [Patent Document 6] JP 2023-81860 A Summary of the Invention [Problem to be solved by the invention]
[0007] According to Patent Document 6, it is described that a film having improved strength and excellent tearability can be obtained, but there is still a strong demand for high strength, tearability, and low-temperature heat sealability. In view of the above circumstances, the object of the present invention is to provide a polypropylene resin composition capable of forming a film having high strength corresponding to the melting point and excellent tearability, a method for producing the same, and a film containing the polypropylene resin composition. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that a non-oriented film using a polypropylene resin composition containing a specific linear polypropylene resin (Y) in combination with a branched polypropylene resin (X) having specific properties has high strength commensurate with its melting point and excellent tearability, thereby completing the present invention. The present invention relates to the following: <1> ~ <4> Regarding. <1> A polypropylene resin composition comprising a branched polypropylene resin (X) having the following properties (X-1) to (X-3) and a linear polypropylene resin (Y) having the following property (Y-1), the resin (X) being present in an amount of 1% by mass to 99% by mass relative to 100% by mass of the total mass of the resins (X) and (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 155.0°C. Property (X-3): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): MFR measured at 230°C under a load of 2.16 kg is 0.1 g / 10 min to 10 g / 10 min. <2> The linear polypropylene resin (Y) is a copolymer of propylene and at least one selected from ethylene and an α-olefin having 4 or more carbon atoms. <1> The polypropylene resin composition according to claim 1. <3> A method for producing a polypropylene resin composition, comprising a step of dry-blending a branched polypropylene resin (X) having the following properties (X-1) to (X-3) and a linear polypropylene resin (Y) having the following property (Y-1). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 155.0°C. Property (X-3): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): MFR measured at 230°C under a load of 2.16 kg is 0.1 g / 10 min to 10 g / 10 min. <4> The above <1> or <2> A film comprising the polypropylene resin composition according to claim 1. Effect of the Invention
[0009] According to the present invention, there are provided a polypropylene resin composition capable of forming a film having high strength corresponding to the melting point and excellent tearability, a method for producing the same, and a film containing the polypropylene resin composition. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for a branched polypropylene-based resin (X) used in an example of the present invention and a reference branched polypropylene-based resin (CX) of the prior art having the same level of fluidity as that of the example are plotted. [Diagram 2] FIG. 2 is a diagram illustrating the baseline and intervals of a chromatogram in GPC. [Diagram 3] FIG. 3 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for a branched polypropylene-based resin (X) used in an example of the present invention and a reference branched polypropylene-based resin (CX) of the prior art having the same level of fluidity as that of the example are plotted. [Figure 4] FIG. 4 is a diagram showing an example of an integrated molecular weight distribution curve. [Diagram 5]FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum take-up speed (MaxDraw) at 230°C, and data for a branched polypropylene-based resin (X) used in an embodiment of the present invention and a reference branched polypropylene-based resin (CX) of the prior art having the same level of fluidity as that of the embodiment are plotted. [Figure 6] FIG. 6 is a graph in which the horizontal axis represents Tm and the vertical axis represents Young's modulus, and data for the polypropylene-based resin films shown in each of the Examples and Comparative Examples are plotted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] I. Polypropylene resin composition The polypropylene resin composition of the present invention is characterized in that it contains a branched polypropylene resin (X) having the following properties (X-1) to (X-3) and a linear polypropylene resin (Y) having the following property (Y-1), and the resin (X) is contained in an amount of 1% by mass to 99% by mass relative to 100% by mass of the total mass of the resins (X) and (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 155.0°C. Property (X-3): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): MFR measured at 230°C under a load of 2.16 kg is 0.1 g / 10 min to 10 g / 10 min.
[0012] The polypropylene resin composition of the present invention contains a specific linear polypropylene resin (Y) in combination with a branched polypropylene resin (X) having the above-mentioned properties (X-1) to (X-3), i.e., a specific branched polypropylene resin (X) having specific molecular weight distribution and branching distribution and high Ea corresponding to MFR, and thereby it is possible to form an unstretched film having high strength corresponding to the melting point (Tm) and excellent tearability.
[0013] The linear polypropylene resin (Y) has an MFR of 0.1 g / 10 min to 10 g / 10 min measured at a temperature of 230° C. under a load of 2.16 kg, and is therefore generally suitable for film production in terms of processability in a cast method and film strength. However, when the linear polypropylene resin (Y) is used alone to form a non-oriented film, the strength and tearability in relation to the Tm of the film are insufficient, as shown in the comparative example described later. On the other hand, in the present invention, a linear polypropylene resin (Y) having the specific MFR is combined with a branched polypropylene resin (X) having the specific properties. The branched polypropylene resin (X) has the above characteristics (1) to (3) and has a high Ea in proportion to the MFR. Although the reason is unclear, it is presumed that the branched propylene polymer of the present invention contains multi-branched molecules having a molecular structure in which many branch chains are introduced in the medium to high molecular weight region, but has a branch distribution in which the content of components that do not relax or components that have a long relaxation time is low. The branched polypropylene resin (X) specified as above shows a relaxation time distribution in which there are many components with a relatively short relaxation time and few components with an extremely long relaxation time, so that local orientation crystallization originating from the entanglement point of molecular chains is unlikely to occur, and it is possible to suppress the non-uniformity of orientation crystallization. Therefore, the extensibility that allows the resin to be stretched widely, thinly and uniformly in a molten state is improved, and the strength reduction is suppressed even when the film is thinned. Furthermore, the strength of the film is improved and the film becomes hard, so that the stress applied when cutting is concentrated at the cut, and the tear strength is reduced. In other words, it is considered that the resistance when tearing the film is suppressed, and therefore a non-stretched film with excellent tearability can be obtained.
[0014] The present invention will be described in detail below. In this specification, the use of "to" indicating a range of values means that the values before and after the range include the lower limit and upper limit. In this specification, the upper and lower limit values of the numerical ranges may be arbitrarily combined, and the preferred ranges of the respective properties may be arbitrarily combined. In the present invention, logarithms are expressed in the common logarithm sense, ie, to the base 10. In the present invention, unless otherwise specified, the contents of the branched polypropylene resin (X) and the linear polypropylene resin (Y) in the resin composition are represented by mass ratios when the total mass of the branched polypropylene resin (X) and the linear polypropylene resin (Y) is taken as 100 mass%.
[0015] The polypropylene resin composition of the present invention contains the branched polypropylene resin (X) and the linear polypropylene resin (Y) having the characteristic (Y-1) in an amount of 1% by mass to 99% by mass of the resin (X) relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may further contain other components such as additives described later.
[0016] 1. Branched polypropylene resin (X) The branched polypropylene resin (X) used in the present invention may be a homopolymer of propylene or a copolymer of propylene and at least one selected from ethylene and α-olefins having 4 or more carbon atoms. The at least one comonomer selected from ethylene and an α-olefin having 4 or more carbon atoms may be ethylene and an α-olefin having 4 to 20 carbon atoms, for example, at least one comonomer selected from ethylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene. The branched polypropylene resin (X) used in the present invention may be a propylene polymer consisting of propylene and 0 to 11 mol % of at least one selected from ethylene and α-olefins having 4 or more carbon atoms. The content of the comonomer may be more than 0 mol % or may be 0.5 mol % or more, with the upper limit being 7.5 mol % or less, in the total monomers.
[0017] 1-1. Characteristics of branched polypropylene resin (X) Characteristics (X-1): The branched polypropylene resin (X) used in the present invention has a melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg of 0.1 g / 10 min to 100 g / 10 min in order to maintain production stability and film strength during molding of the branched polypropylene resin composition by a cast method. The MFR is preferably 1.0 g / 10 min or more, and may be 3.0 g / 10 min or more, while the MFR is preferably 80 g / 10 min or less, more preferably 40 g / 10 min or less, and even more preferably 25 g / 10 min or less, and may be less than 10 g / 10 min. In the present invention, the MFR is a value measured by pelletizing the branched polypropylene resin (X) and measuring the MFR at 230° C. and under a load of 2.16 kgf in accordance with JIS K7210-1: 2014. The pelletization is performed in the same manner as in the “granulation” described in the examples below. The MFR of the branched polypropylene resin can be adjusted by (i) changing the temperature and / or pressure during polymerization of the polypropylene resin and / or (ii) adding hydrogen or other chain transfer agents to the monomers during polymerization of the polypropylene resin.
[0018] Characteristics (X-2): The branched polypropylene resin (X) used in the present invention has a melting point (Tm) measured by differential scanning calorimetry (DSC) of less than 155.0° C. When the melting point is in this range, the solidification of the molten resin during molding is delayed, and the extensibility during molding is improved. The branched polypropylene resin (X) used in the present invention has a Tm of preferably 105.0°C to 150.0°C, more preferably 110.0°C to 145.0°C, and even more preferably 120.0°C to 135.0°C, in order to suppress an increase in heat sealing temperature when used as a heat sealing material while maintaining the strength and tearability of the film. In the present invention, Tm and crystallization temperature (Tc) can be determined using a Seiko Instruments Inc. DSC (DSC6200) by packing 5 mg of a sheet-like sample piece into an aluminum pan, heating it from room temperature to 200°C at a heating rate of 100°C / min, holding it at 200°C for 5 minutes, and then cooling it from 200°C to 40°C at a heating rate of 10°C / min to crystallize it, and determining the maximum crystallization peak temperature (°C) as Tc, and then heating it to 200°C at a heating rate of 10°C / min to melt it, and determining the maximum melting peak temperature (°C) as Tm. A sheet-like sample can be obtained by sandwiching a polypropylene resin between press plates, preheating it at 190°C for 2 minutes, pressing it at 5 MPa for 2 minutes, and then cooling it at 0°C and 10 MPa for 2 minutes.
[0019] Characteristics (X-2-2): The branched polypropylene resin (X) used in the present invention preferably has a difference between Tm and Tc (Tm-Tc) measured by DSC of more than 34.0°C and less than 40.0°C. When the difference (Tm-Tc) is within the above range, the polypropylene-based resin remains in a molten state for an adequate length of time during molding, thereby widening the moldable temperature range and preventing adhesions that accumulate in parts of the mold that are easily heated from being mixed into the film as foreign matter, thereby preventing deterioration in the quality of the film. The lower limit of the above difference (Tm-Tc) is preferably greater than 34.0°C, more preferably 34.5°C or higher, and even more preferably 35.0°C or higher. On the other hand, the upper limit of the above difference (Tm-Tc) is preferably 39.0°C or lower, more preferably 38.0°C or lower.
[0020] Tm and Tc are controlled by stereoregularity, regioregularity, and comonomer content. On the other hand, when Tc is high relative to Tm, it is due to the primary structure other than stereoregularity and regioregularity. In particular, when the polymer has a branched structure, it is believed that the branching points promote crystallization, and the more branches there are, the smaller the difference (Tm-Tc) becomes. Therefore, in order to obtain the Tm and the above-mentioned difference (Tm-Tc) of the branched polypropylene resin (X) used in the present invention, there is a method of selecting a complex that optimizes the stereoregularity, regioregularity, and amount of branching, or controlling the degree of supercooling by using a comonomer, etc.
[0021] Characteristics (X-3): From the viewpoint of improving the quality of a film produced by a cast molding method, the branched polypropylene resin (X) used in the present invention has a flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity that satisfy the following formula (1): Ea≧-12.5×log(MFR)+66 Equation (1)
[0022] In general, the viscosity of an object decreases as its temperature increases, and the logarithm of viscosity, lnη, is proportional to the reciprocal of absolute temperature, 1 / T, and it has long been known empirically that it can be expressed by the following formula (Chemical Dictionary, 2nd Edition, "Andrade's Viscosity Formula").
[0023]
number
[0024] This energy term Ea corresponds to the activation energy when the reaction rate in an Arrhenius chemical reaction is considered to be a flow, and is called the flow activation energy. "High Ea" means "the energy required to make the polymer flow is large." In the case of branched polypropylene resin (X), it is considered that if the amount of branches is large or the branch length is long, the molecular chains become more entangled, and the energy required to make the molecular chains flow is large. In other words, Ea mainly depends on the amount and length of long chain branches in the polymer. In the branched polypropylene resin (X) used in the present invention, the relationship between Ea and MFR was specified, focusing on Ea as an index for obtaining appropriate branching characteristics in order to improve the quality and processability of a film produced by a cast molding method.
[0025] The branched polypropylene resin (X) used in the present invention may have an Ea of 55.0 kJ / mol or more, or 58.0 kJ / mol or more, or 70.0 kJ / mol or less, from the viewpoint of improving productivity while maintaining the strength and tearability of the film.
[0026] Satisfying the formula (1) means that the branched polypropylene resin (X) used in the present invention has an Ea obtained by measuring the dynamic viscoelasticity of at least a specific value in proportion to the MFR. The branched polypropylene resin (X) used in the present invention has an Ea value corresponding to the MFR different from that of conventional propylene polymers, that is, satisfies the formula (1). A branched polypropylene resin having too small Ea in relation to the MFR has inappropriate branching properties including the amount of branching, the length of branching, and the distribution of branching. If such a branched polypropylene resin is used, the strength and tearability of the film are reduced, and the extensibility during melting is deteriorated, resulting in reduced productivity of the film. Therefore, the branched polypropylene resin (X) used in the present invention satisfies the above formula (1). More preferably, it may satisfy the following formula (1-2). Ea≧-12.5×log(MFR)+67 Equation (1-2)
[0027] Generally, when the fluidity of the molten resin is increased, Ea decreases, so it is desirable to have a branched polypropylene resin that has both the fluidity required to maintain the strength, tearability, and productivity of the film and Ea, which is an index of branching characteristics suitable for extensibility when melted. A branched polypropylene resin (X) that has excellent fluidity and satisfies formula (1) can be said to have a high balance between the fluidity and branching characteristics of the molten resin. In addition, the above formula is considered to be a function in which Ea is negatively correlated with an increase in MFR, and the relationship between Ea and MFR was approximately determined based on the data of the branched polypropylene resin (X) used in the examples of the present invention and the reference branched polypropylene resin (CX) of the prior art that has the same level of fluidity as the examples. The relationship between Ea and MFR was approximately determined so as to distinguish between the branched polypropylene resin (X) that has both the fluidity required to maintain the strength, tearability, and productivity of the film and extensibility when melted and the reference branched polypropylene resin (CX) that is inferior in this effect (see FIG. 1).
[0028] The branched polypropylene resin (X) used in the present invention is presumed to have a high Ea relative to the MFR since the branching characteristics including the branch amount, branch length and branch distribution are suitable for improving the extensibility when melted.
[0029] The upper limit of Ea in relation to the MFR is not particularly limited, but may satisfy the following formula (1-3) or may satisfy the following formula (1-4). Ea≦-12.5×log(MFR)+82 Equation (1-3) Ea≦-12.5×log(MFR)+77 Equation (1-4)
[0030] Ea is a value calculated from the shift factor (aT) when creating a master curve based on the temperature-time superposition principle in the measurement of melt viscoelasticity by the Arrhenius equation. In the present invention, the master curve is a curve showing the angular frequency (unit: rad / sec) dependency of the melt complex viscosity (unit: Pa·sec) at 200°C. Ea can be determined by the following method. First, for three temperatures of 180°C, 200°C, and 220°C, the melt complex viscosity-angular frequency curve of the branched polypropylene resin (X) at each temperature (T, unit: °C) is obtained. Based on the temperature-time superposition principle, each melt complex viscosity-angular frequency curve is superimposed on the melt complex viscosity-angular frequency curve at 200°C to obtain each shift factor (aT). From each temperature (T) and aT at each temperature (T), a linear approximation formula (formula (2) below) of [ln(aT)] and [1 / (T+273.16)] is calculated by the least squares method. Next, Ea is obtained from the slope m of the linear formula and the following formula (3). ln(aT)=m(1 / (T+273.16))+n Formula (2) Ea = |0.008314 × m| Equation (3) aT: Shift factor Ea: Flow activation energy (unit: kJ / mol) T: Temperature (unit: ℃) The above calculations may be carried out using commercially available software, such as Trios manufactured by TA Instruments. Note that aT is the amount of movement in the x-axis direction when the log-log curve of melt complex viscosity vs. angular frequency at each temperature (T) is moved in the x-axis (angular frequency) and y-axis (melt complex viscosity) directions and superimposed on the melt complex viscosity vs. angular frequency curve at 200°C. The melt complex viscosity-angular frequency curve is measured using a viscoelasticity measuring device (for example, ARES-G2 manufactured by TA Instruments) under a nitrogen atmosphere under the following conditions. The propylene polymer is compression molded at 180°C for 5 minutes while being careful not to trap air bubbles, to obtain a disk-shaped measurement sample having a thickness of 2.0 mm and a diameter of 25 mm. Measurements of the sample are performed at three temperatures, 180°C, 200°C, and 220°C, using parallel disks having a diameter of 25 mm that are kept at each temperature, after which the measurement sample having a thickness of 2.0 mm is compressed to a thickness of 1.5 mm. Geometry: Parallel plate Plate diameter: 25mm Plate spacing: 2mm Strain: 5% Angular frequency: 0.01~100rad / sec
[0031] In the present invention, the Ea and MFR of the branched polypropylene resin (X) can satisfy the above formula (1) by adjusting the polymerization conditions, such as the selection of the catalyst type, the polymerization temperature, the monomer concentration, the amount of hydrogen, etc. Among these, the adjustment is preferably performed by selecting the catalyst type, and although there is no particular restriction, it is appropriate to adjust the Ea and MFR by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.
[0032] Characteristics (X-4): The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M abs It is preferable that the branching index g' (1 million) is 0.60 to 0.75. The branching index g' is given by the ratio of the intrinsic viscosity [η]br of a polymer with long chain branching to the intrinsic viscosity [η]lin of a linear polymer with the same molecular weight ([η]br / [η]lin). When a polymer molecule has long chain branching, the radius of gyration is smaller than that of a linear polymer molecule of the same molecular weight, and the intrinsic viscosity is smaller, so g' is smaller than 1.0. Also, even if the amount of branching is the same, if the branching length is long, the radius of gyration is smaller than that of a linear polymer molecule of the same molecular weight, and the intrinsic viscosity is smaller, so g' is smaller than 1.0. Linear polymers, by definition, have a g' of 1.0. The definition of g' is described in "Developments in Polymer Characterization-4" (JV Dawkins ed. Applied Science Publishers, 1984), and is a known indicator for those skilled in the art. g' was determined by using 3D-GPC. abs can be obtained as a function of In this specification, 3D-GPC refers to a GPC apparatus connected with three detectors, which are a differential refractometer (RI), a viscometer, and a multi-angle laser light scattering detector (MALLS).
[0033] The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M abs Weight average molecular weight (Mw abs ) may be less than 1 million, and Mw abs From M abs It is considered preferable to have a branched structure in the high molecular weight region of Mn = 1 million because it has high melt tension and reduces neck-in of the film. Neck-in refers to the difference between the width of the film or sheet when the resin is extruded from the die of the extruder and the width of the film or sheet just after it leaves the die. Therefore, the branched polypropylene resin (X) used in the present invention has a g' (1 million) of preferably 0.75 or less, more preferably 0.74 or less, and even more preferably 0.72 or less. abs If a branch structure is adequately present in the high molecular weight region of g'(1 million) and the branch chain length of the introduced branch structure is adequate, the amount of components with extremely long relaxation times is prevented from increasing too much, and extensibility can be maintained, which is believed to enable the line speed during film molding to be increased to improve productivity. Therefore, g'(1 million) is preferably 0.60 or more, more preferably 0.62 or more, and even more preferably 0.65 or more. In this way, the branched polypropylene resin (X) used in the present invention has M abs It is believed that the amount of components with branched structures in the molecular weight region of 100,000,000 is appropriately large within a specific range, which increases the melt strength and increases the strain hardening index (SHI) and melt tension (MT) in the measurement of extensional viscosity as nonlinear viscoelastic properties. Even if the number of branches is large as a whole polymer, the amount of M corresponding to the high molecular weight component is abs If the amount of components having branches in the M = 1 million portion is small, it is difficult to increase the SHI. abs= 1 million, and furthermore, the branched chain length of the introduced branched structure is not too long, which is thought to suppress a decrease in film productivity due to a deterioration in extensibility.
[0034] Characteristics (X-4-2): The branched polypropylene resin (X) used in the present invention is considered to maintain extensibility by the moderate presence of components with long relaxation times, as in the case of the above characteristic (X-4), and to be able to improve the productivity of the film by increasing the line speed during film molding. Therefore, in the molecular weight distribution curve obtained by 3D-GPC, Mw abs Branching index g'(Mw abs ) may be 0.70 to 0.90. g'(Mw abs The lower limit of may be 0.73 or more, or 0.75 or more, and the upper limit may be 0.87 or less, or 0.86 or less.
[0035] Characteristics (X-4-3): The branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs ) and g' (1 million) may satisfy the following formula (3): 0.10≦g'(Mw abs )-g'(1 million) Formula (3) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs ) and g' (million), there are more components with long relaxation times, which is thought to increase the melt strength and reduce neck-in during film molding. Furthermore, the branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs ) and g' (1 million) may satisfy the following formula (3-2). g'(Mw abs )-g'(1 million)≦0.20 Formula (3-2) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs It is considered preferable that the difference between g (million) and g' (million) is not too large, since the proportion of components with extremely long relaxation times will not be too high, improving extensibility and enabling the line speed during film molding to be increased to improve productivity. In addition, since the branched polypropylene-based polymer of the present invention has a branching distribution within the above range, the balance between melt strength and extensibility as a whole is maintained, and the line speed can be increased while reducing neck-in during film molding, thereby improving film productivity, which is considered to be preferable.
[0036] M abs The method for measuring the molecular weight distribution and the branching index at each molecular weight is as follows: The detectors are connected in the order of MALLS, RI, and Viscometer. Equipment: Alliance GPCV2000 (GPC equipped with RI and Viscometer) manufactured by Waters, DAWN-E (MALLS) manufactured by Technology Column: Tosoh GMHHR-H(S)HT (2 columns) Mobile phase solvent: 1,2,4-trichlorobenzene (with antioxidant Irganox 1076 (BASF Japan) added at a concentration of 0.5 mg / mL) ·Measurement temperature: 140℃ ·Flow rate: 1mL / min Sample concentration: 1mg / mL ·Injection volume: 0.2175mL To calculate Mabs obtained from MALLS, the root mean square radius of gyration (Rg), and the intrinsic viscosity ([η]) obtained from Viscometer, the data processing software ASTRA (version 4.73.04) attached to MALLS is used, and calculations are performed with reference to the following literature. References: 1.Developments in Polymer Characterization, vol.4. Essex: Applied Science; 1984. Chapter1. 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000) g' is calculated as the ratio ([η]br / [η]lin) of the intrinsic viscosity ([η]br) obtained by measuring a sample with the above-mentioned Viscometer to the intrinsic viscosity ([η]lin) obtained by separately measuring a linear polymer. Here, [η]lin is obtained using a commercially available homopolypropylene (Novatec PP (registered trademark) grade name: FY6 manufactured by Japan Polypropylene Corporation) as the linear polymer. The fact that the logarithm of [η]lin of a linear polymer has a linear relationship with the logarithm of the molecular weight is known as the Mark-Houwink-Sakurada equation, so the value of [η]lin can be obtained by appropriately extrapolating to the low molecular weight side or the high molecular weight side.
[0037] In the present invention, the g' (million) and g' (Mw abs ), g'(Mw abs As explained in the characteristic (X-3), )-g' (million) can be adjusted by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc. Among them, it is preferable to adjust by selecting the catalyst type, and although there is no particular limitation, it is appropriate to adjust by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.
[0038] Among them, g'(Mw abs It is preferable that the condition where (g)-g' (million) satisfies the formula (3) or the formula (3-2) is adjusted by selecting a catalyst from a plurality of catalyst species or a plurality of metallocene compounds. For example, when a catalyst of a single catalyst type or a single metallocene compound (hereinafter, collectively referred to as a single catalyst) is used instead of a catalyst of multiple catalyst types or multiple metallocene compounds, it is considered that formula (3) or formula (3-2) is not satisfied. This is because, with a single catalyst, the molecular weight distribution of the macromonomer produced is narrow, and macromonomers with significantly different molecular weights are not supplied, so the value of formula (3) is expected to be small, or the value of formula (3-2) to be large. To explain this using Reference Example 2 as an example (see Table 3), g'(Mw abs ) is large, so Mw abs Since there are no components with short branched chains, it is estimated that the molecular weight of the macromonomer produced by this catalyst is high. On the other hand, since g' (1 million) is small, it is assumed that the molecular weight of the macromonomer produced by this catalyst is high. abs It is estimated that there are branched components due to macromonomers with large molecular weights in the range of g'(Mw = 1 million). Thus, in a single catalyst that produces macromonomers with a narrow molecular weight distribution, for example, abs )-g' (million) becomes large and equation (3-2) is not satisfied.
[0039] Characteristics (X-5): The branched polypropylene resin (X) used in the present invention preferably has a ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) of 2.0 to 4.0. Mz, Mw, and number average molecular weight (Mn) are each indices that represent the average molecular weight of a polymer. Mz is an index of the average molecular weight with a high specific gravity on the high molecular weight side, Mn is an index of the average molecular weight with a high specific gravity on the low molecular weight side, and Mw is an index of the average molecular weight in between. In addition, the respective ratios, Mw / Mn and Mz / Mw, are indices of the spread of the molecular weight distribution of the polymer. In the branched polypropylene resin (X), since a component having a long relaxation time is present in an appropriate amount and a decrease in melt tension is suppressed to reduce neck-in of the film, Mz / Mw is preferably 2.0 to 4.0. The upper limit of Mz / Mw is more preferably 3.6 or less, even more preferably 3.4 or less, and even more preferably 3.2 or less. The lower limit of Mz / Mw is more preferably 2.3 or more, even more preferably 2.8 or more, and even more preferably 2.9 or more.
[0040] In addition, the branched polypropylene resin (X) used in the present invention may have a ratio of Mw to Mn (Mw / Mn) obtained by GPC of 3.0 to 7.0 from the viewpoint of production stability during molding of the branched polypropylene resin composition by a cast method. The upper limit of Mw / Mn may be 6.0 or less, 5.0 or less, 4.5 or less, or 4.3 or less. On the other hand, the lower limit of Mw / Mn may be 3.2 or more, or 3.3 or more. Furthermore, from the viewpoint of production stability during molding of the branched polypropylene resin composition by a cast method, the Mw of the branched polypropylene resin (X) used in the present invention may be 150,000 to 350,000, 180,000 to 330,000, or 200,000 to 320,000.
[0041] The values of Mz, Mw, Mn, Mw / Mn, and Mz / Mw are all obtained by GPC. The details of the measurement method and measuring equipment are as follows. Apparatus: Waters GPC (ALC / GPC, 150C) Detector: FOXBORO MIRAN, 1A, IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AT-806MS (3 columns) Mobile phase solvent: o-dichlorobenzene (ODCB) ·Measurement temperature: 140℃ ·Flow rate: 1.0mL / min ·Injection volume: 0.2mL The measurement sample is prepared as follows: A 1 mg / mL solution is prepared using the sample and ODCB (containing 0.5 mg / mL dibutylhydroxytoluene (BHT)), and the sample is dissolved at 140° C. for about 1 hour to prepare the measurement sample. The baseline and intervals of the obtained chromatogram are defined as shown in Figure 2. The retention volume obtained by GPC measurement is converted to molecular weight using a calibration curve prepared in advance using standard polystyrenes, all of which are the following brands manufactured by Tosoh Corporation: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000. Each standard was dissolved in ODCB (containing 0.5 mg / mL BHT) to a concentration of 0.5 mg / mL, and 0.2 mL of the solution was injected to create a calibration curve. The calibration curve was calculated using a cubic equation obtained by approximating the curve using the least squares method. Viscosity formula used for conversion to molecular weight: [η] = K × M α The following numerical values are used: PS:K=1.38×10 -4 , α=0.7 PP:K=1.03×10 -4 , α=0.78
[0042] The average molecular weight, molecular weight distribution (Mz, Mw, Mn, Mw / Mn, Mz / Mw) and balance thereof of the branched polypropylene resin (X) measured by GPC can be adjusted by polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc.
[0043] Characteristics (X-5-2): The branched polypropylene resin (X) used in the present invention preferably has an integral molecular weight distribution curve obtained by GPC such that the ratio (W2 million / W1 million) of the proportion of components having a molecular weight of 2 million or more (W2 million) to the proportion of components having a molecular weight of 1 million or more (W1 million) satisfies the following formula (4): (W2 million / W1 million)<-0.05×log(MFR)+0.34 Formula (4) W2 million / W1 million is the ratio of the amount of components with even higher molecular weights to the amount of components in the high molecular weight range. In the above formula (4), W2 million / W1 million is considered to be a function negatively correlated with an increase in MFR, and the relationship between W2 million / W1 million and MFR was approximately determined based on the data of the branched polypropylene resin (X) used in the examples of the present invention and the reference branched polypropylene resin (CX) of the prior art having the same level of fluidity as the examples. The relationship was approximately determined so as to distinguish the branched polypropylene resin (X) that has both the fluidity required to maintain the strength, tearability, and productivity of the film and the extensibility when melted from the reference branched polypropylene resin (CX) that is inferior in these effects (see FIG. 3). Satisfying the formula (4) means that W2 million / W1 million is less than a specific value in terms of MFR. In other words, it means that the amount of components with a molecular weight of 2 million or more, which is higher than the amount of components with a molecular weight of 1 million or more, is relatively small. When W2 million / W1 million is in the above range in terms of MFR, it is considered that the amount of components with long relaxation times is suppressed to be excessive, and extensibility is maintained, so that the line speed during film molding can be increased to improve productivity. Therefore, it is preferable that the branched polypropylene resin (X) used in the present invention satisfies the above formula (4). The branched polypropylene resin (X) used in the present invention more preferably satisfies the following formula (4-2), and further preferably satisfies the following formula (4-3). (W2 million / W1 million)<-0.05×log(MFR)+0.28 Formula (4-2) (W2 million / W1 million)<-0.05×log(MFR)+0.20 Formula (4-3)
[0044] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00% by mass to 9.50% by mass. When the branched polypropylene resin (X) used in the present invention has a W1 million within the above range, it contains a moderate amount of high molecular weight components and exhibits excellent extensibility while maintaining the melt tension required for molding. As a result, it is possible to increase the line speed while reducing neck-in during film molding, and it is believed that the productivity of the film is improved. Thus, the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00% by mass to 9.50% by mass, or 2.00% by mass to 6.00% by mass.
[0045] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass % or less. As in the above, it is believed that when the amount of components in the very high molecular weight range is moderate, components with extremely long relaxation times are moderately maintained and extensibility is also maintained, so that the line speed during film molding can be increased and film productivity is improved. Therefore, in the present invention, attention is focused on components with a molecular weight of 2 million or more, and the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass% or less, 1.00 mass% or less, or 0.70 mass% or less. The branched polypropylene resin (X) used in the present invention may have a W2 million of 0.05 mass% or more.
[0046] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.25 or less, 0.20 or less, or 0.17 or less. As mentioned above, when W2 million / W1 million is within the above range, the components with long relaxation times are prevented from becoming too numerous, and extensibility is maintained, so that the line speed during film molding can be increased, and film productivity is thought to improve. The branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.02 or more, 0.03 or more, or 0.05 or more.
[0047] In the present invention, W1 million and W2 million are defined as the value obtained by subtracting from 1 the integral value up to a molecular weight (M) of 1 million (Log(M)=6.0) and up to a molecular weight (M) of 2 million (Log(M)=6.3) in an integrated molecular weight distribution curve (total amount normalized to 1) obtained by GPC, and multiplying the result by 100. An example of an integrated molecular weight distribution curve is shown in FIG. In the present invention, W1 million and W2 million of the branched polypropylene resin (X) can be adjusted by polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and amount of hydrogen, in the same manner as described for characteristic (X-3).
[0048] Characteristics (X-6): The branched polypropylene resin (X) used in the present invention is 13 The meso triad fraction (mm) measured by C-NMR is preferably 95.0% or more and less than 99.0%. Characteristics (X-6-2): In addition, the branched polypropylene resin (X) used in the present invention preferably has a heterogeneous bond ([2,1 bond]) content of 0 mol % to 0.30 mol % and a heterogeneous bond ([1,3 bond]) content of 0 mol % to 0.25 mol %.
[0049] The crystallinity of the branched polypropylene resin (X) is affected by the stereoregularity indicated by the mesotriad fraction (mm) and mesopentad fraction (mmmm) and the regioregularity indicated by [2,1 bond] and [1,3 bond]. In other words, crystallization proceeds by folding back the lamellae from the irregularity-defective parts (sterically irregular bonds and heterogeneous bonds). When the branched polypropylene resin (X) used in the present invention has a stereoregularity and a regioregularity within the above ranges, it is believed that the fluidity of the resin during gradual cooling and solidification during molding and the melt tension during solidification are improved due to a crystallization process caused by shear or elongation deformation.
[0050] Therefore, from the viewpoint of improving the melt tension of the branched polypropylene resin (X) when solidified, reducing neck-in during film molding, and improving the productivity of the film, mm of the branched polypropylene resin (X) used in the present invention is preferably 95.0% or more, more preferably 96.0% or more, and even more preferably 97.0% or more. On the other hand, if mm is too high, the strength of the film may become too high and the stiffness may become too strong. Therefore, mm of the branched polypropylene resin (X) used in the present invention is preferably less than 99.0%, more preferably 98.5% or less, and more preferably 98.2% or less.
[0051] Similarly, from the viewpoint of improving the melt tension at the time of solidification, reducing neck-in during film molding, and improving the productivity of the film, the [2,1 bond] content of the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.30 mol%, more preferably 0 mol% to 0.25 mol%, even more preferably 0 mol% to 0.20 mol%, even more preferably 0.030 mol% to 0.25 mol%, and particularly preferably 0.05 mol% to 0.20 mol%. The upper limit of the [2,1 bond] content may be 0.15 mol% or less. In combination with the above-mentioned [2,1 bond] content, the [1,3 bond] content of the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.25 mol%, more preferably 0 mol% to 0.20 mol%, even more preferably 0 mol% to 0.15 mol%, still more preferably 0.05 mol% to 0.20 mol%, and particularly preferably 0.10 mol% to 0.15 mol%.
[0052] 13 The methods for measuring and calculating the amounts of mm, [2,1 bond] and [1,3 bond] measured by C-NMR are as follows. A 200 mg sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene (C6D5Br) = 3 / 1 (volume ratio) and hexamethyldisiloxane, a chemical shift standard substance, and dissolved uniformly in a block heater at 150 °C to prepare a measurement sample. (1 H-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 4.5° Pulse Interval: 2 seconds Number of times of accumulation: 1024 times Chemical shift: The chemical shift is set to 0.09 ppm for the proton signal of hexamethyldisiloxane, and the chemical shifts of the signals due to other protons are based on this. ( 13 C-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 45° Pulse Interval: 18.0 seconds Number of times accumulated: 3072 Decoupling conditions: Broadband decoupling method Chemical shift: Chemical shifts of hexamethyldisiloxane 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals are based on this.
[0053] <stereoregularity> The meso triad fraction (mm) of three propylene units is 13 Measured by C-NMR 13 The integrated intensity of the C signal is calculated by substituting it into the following equation (5). mm(%)=I mm ×100 / (I mm +3×I mrrm ) Formula (5) Here I mm is assigned to the mm bonding mode of three propylene units. 13 The integrated intensity of the C signal is shown in Fig. 1. The integrated intensity of the signal with a chemical shift in the range of 23.6 to 21.1 ppm (hereinafter referred to as "I 23.6~21.1" is used as the calculation. Spectral assignment can be done with reference to Polymer Jounral, vol. 16, p. 717 (1984), Asakura Publishing, Macromolecules, vol. 8, p. 687 (1975), and Polymer, vol. 30, p. 1350 (1989). The chemical shift range shifts slightly depending on the molecular weight of the polymer, but it is easy to distinguish the regions.
[0054] A specific method for determining mm will be described below. The signals derived from the methyl group of the central propylene unit of the head-to-tail (1,2 bond) triplet chain centered on a propylene unit occur in three regions depending on their configuration. I mm =:I 24.3~21.1 I mr+rm =:I 21.1~20.5 I rr =:I 20.5~19.8 Although the chemical shift range of each region shifts slightly depending on the molecular weight and monomer composition of the copolymer, the above three regions are easily distinguishable. Here, mm, mr+rm, and rr are represented by the following structural formulas (1-a) to (1-c), respectively.
[0055] [ka]
[0056] In addition, the following structural formulae (2-a) to (2-d) may be present as partial structures containing positionally irregular units resulting from heterogeneous bonds such as 2,1 bonds and 1,3 bonds. Structural formulas (2-a), (2-a), and (2-a) are structures based on a 1,2 bond, and structural formula (2-d) is a structure based on a 1,3 bond.
[0057] [ka]
[0058] Of these, the carbon A, A', A'', and T signals appear in the mr+rm region, and the carbon B and B' signals appear in the rr region. It should be noted that the carbon C and C' signals appear in the vicinity of 17.5 to 17.1 ppm, but they do not need to be taken into consideration as they are not related to the mm, mr+rm, and rr regions of interest. Therefore, when calculating the mm fraction using formula (5), it is necessary to subtract the signal areas based on carbons A, A', A'', B, B', and T that are not based on head-to-tail bonded triads from the signal areas in the mr+rm region and the rr region, respectively.
[0059] The signal area based on carbon A can be evaluated from the signal areas of carbon C (resonating at about 17.1 ppm), carbon C' (resonating at about 17.5 ppm), carbon E (resonating at about 35.7 ppm), carbon G (resonating at about 35.8 ppm), and carbon D (resonating at about 42.1 ppm) in the positional irregular partial structure [structural formula (2-a)] using the following formula. I A =(I C +I C’ +I E +I G +I D ) / 5 The signal area based on carbon A' can be evaluated from the signal areas of carbons H and I (resonating near 34.7 to 34.5 ppm) of the regioirregular partial structure [structural formula (2-b)] according to the following formula. I A’ =(I H +I I ) / 2 The signal area based on carbon B can be evaluated from the signal areas of carbons H and I (resonating near 34.7 to 34.5 ppm) of the regioirregular partial structure [structural formula (2-b)] according to the following formula. I B =(I H +I I ) / 4 The signal areas based on carbon A'' and carbon B' can be evaluated using the signal areas of carbons O and N (resonating at around 34.9 ppm) of the regioregular partial structure [structural formula (2-c)] according to the following formula. I A”=I B’ =I O,N / 2 The signal area based on carbon T can be evaluated using the signal area of carbon L (resonating at about 27.6 ppm) from the following formula. I T =I L
[0060] The branched polypropylene resin (X) used in the present invention may have a partial structure represented by the following structural formulas (3-a) to (3-b).
[0061] [ka]
[0062] The methyl group of the central propylene unit of the partial structure PPE+EPP (PPE+EPP-methyl group) resonates in the mr+rm region, and the methyl group of the central propylene unit of the partial structure EPE (EPE-methyl group) resonates in the rr region. Therefore, when such partial structures are present, it is necessary to subtract the signal areas based on the PPE+EPP-methyl group and the EPE-methyl group from the signal areas in the mr+rm and rr regions. The signal area based on the PPE+EPP-methyl groups can be evaluated from the signal area of the corresponding methine group (resonating at about 30.8 ppm), and the signal area based on the EPE-methyl group can be evaluated from the signal area of the corresponding methine group (resonating at about 33.2 ppm). From the above, the signal areas of mm, mr+rm, and rr can be evaluated, and the mm fraction of the three-unit sequence consisting of head-to-tail bonds with the propylene unit at the center can be calculated according to the above formula (5).
[0063] <Positional regularity> The amount of [2,1 bond] and [1,3 bond] is 13 Measured by C-NMR 13 It is calculated using the integrated intensity of the C signal according to the following formula. [2,1 bond] amount (mol%)=I 2,1-P ×100 / (I 1,2-P +I2,1-P +I 1,3-P ) [1,3 bond] amount (mol%)=I 1,3-P ×100 / (I 1,2-P +I 2,1-P +I 1,3-P ) Here, I 1,2-P is the integrated intensity of the 13C signal resonating in the 49.0-44.4 ppm region, which is assigned to the [1,2 bond] of the propylene unit, and I 2,1-P is the signal intensity assigned to the [2,1 bond] represented by structural formulas (2-a) to (2-c), I 1,3-P is calculated from the signal intensity assigned to the [1,3 bond] represented by structural formula (2-d) according to the following formula: I 1,2-P =I 49.0~44.4 I 2,1-P =I A +I B +I A” I 1,3-P =I T / 2
[0064] Characteristics (X-6-3): Moreover, the branched polypropylene resin (X) used in the present invention preferably has an ethylene content of 0 mol % to 11 mol %. The ethylene content can be calculated by the following formula. Ethylene content (mol%) = I E ×100 / (I E +I p ) Here, I P is expressed by the following formula: I P =I 1,2-P +I 2,1-P +I 1,3-P I E represents the characteristic value of ethylene based on the bond with ethylene and is expressed by the following formula: I E =(I 25.0~24.0 +I 30.0~29.8 +I O,N ) / 2+(I 38.2~37.2 -I T +3×I27.3~27.1 +I 30.5.~30.2 -I A -I npr +I H +I I ) / 4
[0065] The above properties (X-6), (X-6-2) and (X-6-3) can be satisfied by adjusting polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration and hydrogen amount.
[0066] Characteristics (X-7): The branched polypropylene resin (X) used in the present invention has the following properties: 13 The number of long chain branches (LCB number) measured by C-NMR is preferably 0.1 to 0.5 per 1000 monomers.
[0067] [ka] [In structural formula (A), P 1 , P 2 , P 3 are propylene-based polymer residues, each having more than one propylene unit, C br indicates the methine carbon at the root of a branched chain having 7 or more carbon atoms, and C a , C b , C c is the methine carbon (C br ) to indicate the methylene carbon adjacent to the In the structural formula (A), the main chain of the propylene polymer is P 1 -C br -P 2 Line, P 1 -C br -P 3 Line or P 2 -C br -P 3 Therefore, there are three types of lines, C br -P 3 Line C br -P 2 Line or C br -P 1The line can be the branched chain. 1 , P 2 , P 3 In itself, C described in structural formula (A) br Another branched carbon (C br ) may also be included. Here, the assignment of the LCB structure is 13 C-NMR revealed three methylene carbons (C a , C b , C c ) was observed, and methine carbon (C br ) is observed as C br It is characterized by the fact that the three adjacent methylene carbons are observed to be separated into three diastereotopic, unequal carbons. Also, the LCB number is: 13 The methine carbon at the base of a branched chain with 7 or more carbon atoms per 1,000 monomer units (C br Branched chains with more than 6 carbon atoms can be distinguished from branched chains with 6 or fewer carbon atoms by the difference in the peak position of the methine carbon at the base of the branch (see Macromol. Chem. Phys. 2003, Vol. 204, p. 1738). The LCB number is the number of methylene carbons (C) in the propylene main chain at 44.1-43.9 ppm, 44.8-44.7 ppm, and 44.9-44.8 ppm when the intensity of the methylene carbons in the propylene main chain at 49.0-44.4 ppm is normalized to 1000. a , C b , C c ) and the average of the signal integrated intensities of the methine carbon (Cbr) at 31.8 to 31.6 ppm, calculated using the following formula, and expressed as the number per 1,000 propylene monomer units. LCB=[(I 44.1~43.9 +I 44.8~44.7 +I 44.9~44.8 +I 31.8~31.6 ) / 4] / I 49.0~44.4
[0068] The characteristic (X-7) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-3).
[0069] Characteristics (X-8): The branched polypropylene resin (X) used in the present invention has a strain hardening index (SHI@1s -1 ) is preferably 0.70 to 2.50. Here, SHI@1s -1 is the extensional viscosity (η E In the measurement of the Hencky strain (ε) between 1 and 3, the horizontal axis is the logarithm of the Hencky strain (log(ε)) and the vertical axis is the logarithm of the extensional viscosity (log(η E ) is the slope when plotting In order to increase the melt tension to improve moldability and to improve the productivity of the film by providing excellent extensibility, the SHI@1s of the branched polypropylene resin (X) used in the present invention is -1 is preferably from 0.70 to 2.50, more preferably from 0.80 to 2.00, and further preferably from 1.00 to 1.80. Branched polypropylene resin (X) is SHI@1s -1 When SHI@1s is relatively large, the extensional viscosity increases due to the presence of components in the polymer that do not relax at high strain rates. Therefore, linear polymers that do not have strain hardening at high strain rates and SHI@1s -1 It is considered that the branched polypropylene resin (X) used in the present invention has a higher SHI@1s than a polymer having a smaller SHI@1s, and therefore has a higher melt tension, and hence is more easily moldable in sheet molding, blow molding, thermoforming, and foam molding. -1 It is preferable that the ratio is 0.70 or more. Branched polypropylene resin (X) is SHI@1s -1When SHI@1s is appropriately large, the amount of components that do not relax or components that relax for a long time is appropriately maintained, and the local progression of oriented crystallization starting from the entanglement points of molecular chains is suppressed, thereby maintaining extensibility. From this viewpoint, the branched polypropylene resin (X) used in the present invention has SHI@1s -1 It is preferable that the ratio is 2.50 or less.
[0070] The strain hardening index (SHI) can be determined by measuring the uniaxial extensional viscosity as described in Polymer, Vol. 42, p. 8663 (2001). In the present invention, SHI@1s -1 is measured by the following method. Equipment: TA Instruments ARES-G2 Fixture: TA Instruments Extensional Viscosity Fixture ·Measurement temperature: 180℃ ·Strain rate: 1.0 / sec - Preparation of test specimen: A sheet of 18 mm x 10 mm and 0.7 mm thick was prepared by press molding.
[0071] To calculate the SHI, the above measurement method is used to obtain data on the time change in elongational viscosity at a predetermined constant strain rate, and the measurement data is plotted as log(ε) on the horizontal axis and log(η) on the vertical axis. E ) is plotted on a graph. Then, the slope of the extensional viscosity in the Hencky strain range between 1 and 3 is identified from the graph, and this slope is taken as the SHI at the strain rate under the measurement conditions.
[0072] In order to satisfy the characteristic (X-8), the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc. can be adjusted in the same manner as described for the characteristic (X-3).
[0073] Characteristics (X-9): The branched polypropylene resin (X) used in the present invention has excellent extensibility while maintaining the melt tension necessary for molding, thereby improving the productivity of the film, and therefore preferably has a multi-branching index (MBI) of 0.10 to 1.00. The lower limit of the MBI is more preferably 0.18 or more, and the upper limit is more preferably 0.80 or less, and further preferably 0.60 or less. Here, MBI is the slope of a plot of the SHI of a polymer at strain rates of 0.1 / sec to 10 / sec, with the logarithm of the strain rate (log(dε / dt)) on the horizontal axis and the SHI at strain rates of 0.1 / sec to 10 / sec on the vertical axis. The SHI of a polymer changes with strain rate. The MBI indicates the dependence of the SHI on the strain rate. A larger MBI value means that the SHI increases more with increasing strain rate. To obtain the MBI, SHI is measured at multiple strain rates in the range of 0.1 / sec to 10 / sec, and the SHI at each strain rate is plotted on a graph with log(dε / dt) on the horizontal axis and SHI on the vertical axis. The slope of the approximation line of the plot in the range of strain rates from 0.1 / sec to 10 / sec is defined as the MBI. -1 , SHI@1.0s -1 , SHI@10.0s -1 The slope of the line obtained by approximating the plot of the three points using the least squares method was determined as the MBI.
[0074] The characteristic (X-9) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-3).
[0075] Characteristics (X-10): The branched polypropylene resin (X) used in the present invention has excellent extensibility while maintaining the melt tension necessary for molding, and therefore can increase the line speed during film molding to improve film productivity. From this viewpoint, the melt tension (MT) at 230°C may be 0.3 g to 15 g, or may be 0.5 g to 15 g. In the present invention, MT is defined as the tension detected at a pulley when a resin is extruded in a string-like form and wound around a roller under the following conditions using a melt tension tester (for example, Capilograph 1B manufactured by Toyo Seiki Seisakusho). ·Resin temperature: 230℃ Capillary: diameter 2.0mm, length 40mm Cylinder diameter: 9.55mm Cylinder extrusion speed: 20mm / min · Winding speed: 4.0m / min If the resin breaks at a winding speed of 4.0 m / min, the melt tension is deemed "unable to evaluate."
[0076] Characteristics (X-11): The branched polypropylene resin (X) used in the present invention may have a maximum draw speed (MaxDraw) m / min at 230° C. and an MFR that satisfy the relationship represented by the following formula (6). (MaxDraw)>200×log(MFR)-38 Equation (6) Here, MaxDraw is the melt tension measurement, in which the resin is extruded into a string shape and wound around a roller, and the winding speed is increased from 4.0 m / min to an acceleration of 18.1 mm / sec. 2 This is the winding speed just before the string-shaped resin breaks when the winding speed is gradually increased. If the resin breaks at a winding speed of 4.0 m / min, it is deemed "evaluation not possible." The melt extensibility can be evaluated using MaxDraw as an index, and the larger MaxDraw is, the better the extensibility is. In the present invention, MaxDraw was measured under the following conditions. Equipment: INSTRON capillary rheometer CEAST SR50 Capillary: diameter 2.0mm, length 40mm Barrel diameter: 15mm Barrel length: 290mm Cylinder extrusion speed: 20mm / min ·Resin temperature: 230℃
[0077] Generally, when the fluidity is increased, the extensibility is excellent but the melt tension is decreased, and when the fluidity is increased to provide excellent extensibility, the melt tension is insufficient. Therefore, it is desirable for the polypropylene resin to have both the melt tension required for molding and excellent extensibility. By using such a polypropylene resin, the line speed can be increased while reducing neck-in during film molding, thereby improving the productivity of the film. The relationship between MaxDraw and MFR defined by the above formula (6) can be used as an index of extensibility commensurate with fluidity. Satisfying the above formula (6) indicates that the branched polypropylene resin (X) used in the present invention has excellent extensibility commensurate with fluidity. That is, the MaxDraw is considered to be a function having a positive correlation with an increase in MFR, and the parameters of the relational equation between MaxDraw and MFR are determined by the least squares method based on the data of the branched polypropylene resin (X) used in the examples and the reference branched polypropylene resin (CX) of the prior art having the same level of fluidity as the examples (see FIG. 5).
[0078] 1-2. Manufacturing method of branched polypropylene resin (X) The method for producing the branched polypropylene resin (X) used in the present invention is not particularly limited as long as it is a method that can produce a branched polypropylene resin (X) having the above-mentioned properties that are characteristic of the present invention. However, a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is suitable. The present inventors speculate that the mechanism of the macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is as follows. When polymerization is performed using a catalyst containing a metallocene compound (referred to as compound 1) that forms a catalyst that mainly produces a macromonomer and a metallocene compound (referred to as compound 2) that forms a catalyst that mainly copolymerizes a macromonomer and a propylene monomer to produce a polymer having a branched chain, the following polymerization behavior is observed. By using a propylene polymerization catalyst containing compound 1 and compound 2, it is possible to obtain a polymer having a molecular weight range that includes a molecular weight distribution that is a combination of the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 1 (catalyst 1) and the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 2 (catalyst 2). In the process of forming the branched structure, when the polymer produced from catalyst 1 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 1), and further, a copolymer of propylene and macromonomer 1 is produced from catalyst 1, and a copolymer of propylene and macromonomer 1 is produced from catalyst 2. When the polymer produced from catalyst 2 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 2), and further, a copolymer of propylene and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene and macromonomer 2 is produced from catalyst 2. Furthermore, when the polymer produced from catalyst 1 is macromonomer 1 and the polymer produced from catalyst 2 is macromonomer 2, furthermore, a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 2. In this way, depending on the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 1 of the polymer produced from catalyst 1, the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 2 of the polymer produced from catalyst 2, the quantitative ratio and steric positional relationship between catalyst 1 and catalyst 2, the average molecular weight, high molecular weight, and very high molecular weight of the branched polypropylene resin (X) as the final product, as well as the amount and branch distribution, change. That is, Mn, Mw, Mz, W 1 million, W 2 million, g' (1 million), g' (Mw abs ), [g'(Mw abs )-g'(million)], Ea, SHI, MBI, MT, etc. are expected to change.
[0079] A preferred method for producing the branched polypropylene resin (X) used in the present invention is, but is not limited to, the following method. In the method for producing the branched polypropylene resin (X) used in the present invention, from the viewpoint of easily satisfying the above-mentioned characteristics, it is preferable to carry out polymerization using a polymerization catalyst in which two catalyst components, component [A-1] and component [A-2], which generate a macromonomer, are used and the types, amounts and amount ratio of component [A-1] and component [A-2] are selected and combined so that the following conditions are satisfied: a) The molecular weight of the polymer produced from component [A-2] is higher than that of the polymer produced from component [A-1], b) The proportion of terminal vinyl in the polymer produced from component [A-1] is greater than the proportion of terminal vinyl in the polymer produced from component [A-2]; c) Component [A-2] has better copolymerizability with the macromonomer than component [A-1].
[0080] The propylene polymerization catalyst for producing the branched polypropylene resin (X) used in the present invention preferably contains the following components [A-1], [A-2], [B] and [C]. Component [A-1]: a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerized at 70°C; Component [A-2]: A metallocene compound which, when propylene homopolymerized at 70°C, gives a propylene homopolymer a-2 having a larger Mn than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and less than 0.5. Component [B]: a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair Component [C]: Organoaluminum compound
[0081] Component [A-1] is a metallocene compound that gives a propylene homopolymer a-1 with an Rv of 0.5 or more when propylene homopolymerization is carried out at 70°C. Component [A-1] is preferably a metallocene compound with an Rv of 0.65 or more, more preferably 0.75 or more, and ideally 1.0 (one end of all molecular chains has a vinyl structure). By using a metallocene compound that forms a polymerization catalyst for producing a propylene homopolymer with a higher Rv, a more efficient macromonomer synthesis step can be carried out. Here, the terminal vinyl ratio (Rv) and the terminal vinylidene ratio (Rvd) are defined by the following formulas. Rv = [Vi] / {(total number of terminals - number of LCBs) ÷ 2} Rvd = [Vd] / {(total number of terminals - number of LCBs) ÷ 2} (However, [Vi] and [Vd] are 1 the number of terminal vinyl groups and the number of terminal vinylidene groups per 1000 monomers calculated by 1H-NMR. The total number of terminals is 1 calculated by 1H-NMR and 13 the total number of terminals per 1000 monomers calculated by 13C-NMR. The number of LCBs is 13 the number of LCBs per 1000 monomers calculated by 13C-NMR.)
[0082] [Relationship between reaction mechanism and terminal structure], [Evaluation method of terminal vinyl ratio (Rv) and terminal vinylidene ratio (Rvd)], <Calculation method of the number of saturated terminals>, <Calculation method of the number of unsaturated terminals>, <Calculation method of the number of LCBs>, <Calculation method of the total number of terminals>, and <Calculation method of terminal vinyl ratio (Rv) · terminal vinylidene ratio (Rvd)> can refer to the descriptions in paragraphs 0073 to 0080 of International Publication No. 2022 / 209773. In addition, the polymerization conditions of propylene when determining Rv and Rvd of the catalyst component are as follows. After replacing the inside of the 20L autoclave tank with propylene, 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) is added, 0.51NL of hydrogen is introduced, and 5000g of liquid propylene is introduced. Then, 300mg of a catalyst containing component [A-1] is pumped into the tank (excluding the prepolymerized polymer) to start polymerization, and polymerization is carried out at 70℃ for 1 hour. Finally, the unreacted propylene is quickly purged, and the polymerization is stopped to obtain a propylene polymer.
[0083] Examples of the component [A-1] include bisindenyl complexes having a bulky heterocyclic group at the 2-position of the indenyl group and an aryl group or a heterocyclic group containing a nitrogen, oxygen or sulfur atom that may be substituted at the 4-position. Specific examples of the component [A-1] can be found in paragraphs 0081 to 0088 of WO 2022 / 209773.
[0084] The component [A-2] is a metallocene compound which, when propylene homopolymerized at 70°C, gives a propylene homopolymer a-2 having a larger Mn and an Rv of 0.1 or more and smaller than 0.5 than those of the propylene homopolymer a-1.
[0085] The component [A-2] is a metallocene compound that forms a polymerization catalyst for copolymerizing a propylene monomer and a propylene macromonomer and for producing a propylene macromonomer. Therefore, the component [A-2] is a metallocene compound having an Rv of 0.1 or more, preferably 0.15 or more, and more preferably 0.2 or more. On the other hand, as the component [A-2], a metallocene compound that has a high molecular weight and a low Rv but forms a polymerization catalyst that efficiently copolymerizes a macromonomer is used, thereby making it possible to suppress the generation of high molecular weight branched components with long branches. Therefore, the component [A-2] is a metallocene compound having an Rv of less than 0.5, preferably 0.45 or less, and more preferably 0.3 or less.
[0086] Furthermore, in order to obtain the average molecular weight, molecular weight distribution and branching distribution, which are the characteristics of the branched polypropylene resin (X) used in the present invention, such that Mw, Mz and g' (1 million) have the above-mentioned properties, and preferably W2 million / W1 million satisfies the above-mentioned properties, it is necessary for component [A-2] to produce a polymer having a higher molecular weight than component [A-1]. Therefore, component [A-2] is a metallocene compound that produces a higher molecular weight polymer than component [A-1] when propylene homopolymerization is performed at 70°C with the same amount of hydrogen.
[0087] In order to obtain an average molecular weight, molecular weight distribution and branching distribution such that the branched polypropylene resin (X) used in the present invention satisfies the above-mentioned properties, it is preferable that the component [A-2] has a better copolymerizability of the macromonomer than the component [A-1]. Therefore, it is preferable that component [A-2] is a metallocene compound in which, when propylene is homopolymerized at 70°C, the proportion of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is greater than that of component [A-1].
[0088] By selecting the component [A-2] as described above, it is possible to preferentially cause the reaction in which the macromonomer with a relatively small molecular weight produced in the component [A-1] is copolymerized with the component [A-2]. The evaluation method for Rv and Rvd is the same as that for component [A-1], except that 100 mg of a catalyst containing component [A-2] (excluding the prepolymerized polymer) is used and 1.19 NL of hydrogen is introduced to polymerize. In addition, the Mw characteristics can be evaluated in the same manner as in the evaluation of Rv and Rvd, by performing bulk polymerization at 70°C, measuring the polymers produced from component [A-2] and component [A-1] by GPC, and comparing the Mw values obtained. Furthermore, the copolymerization characteristics of the macromonomer can be evaluated by performing bulk polymerization at 70°C in the same manner as in the evaluation of Rv and Rvd, and comparing the proportion of the number of terminal vinyls produced that have copolymerized into LCBs {LCB number / ([Vi]+LCB number)} obtained by NMR measurement of the polymer produced from component [A-2] and component [A-1].
[0089] As described above, the ratio of macromonomer in the polymer produced from component [A-2] is lower than that in the polymer produced from component [A-1], so the amount of copolymerization of macromonomer 2 is suppressed. On the other hand, since macromonomer copolymerization is better than that of component [A-1], the branch chain length can be adjusted in the introduced branch structure of branched polypropylene resin (X) by efficiently copolymerizing macromonomer 1. By utilizing this branch chain length adjustment, it is possible to obtain a branched polypropylene resin (X) having the average molecular weight, molecular weight distribution and branch distribution, branch structure, and melt properties (Ea, etc.) resulting therefrom, such that Mw, Mz, and g' (1 million), which are the characteristics of the branched polypropylene resin (X) used in the present invention, satisfy the above-mentioned properties.
[0090] The component [A-2] may be, for example, a metallocene compound of formula (I) described in JP-A-2007-528925. In particular, the component [A-2] may be a metallocene compound of formula (IV) described in JP-A-2007-528925.
[0091] Specific examples of the metallocene compound of formula (IV) described in JP-A-2007-528925 are shown below, but the invention is not limited thereto. Dimethylsilylenebis(cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(5-methyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,3,5-trimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(4-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(2,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-di-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride
[0092] Other examples include compounds in which one or both of the dichlorides in the above-listed compounds are replaced with a bromine atom, an iodine atom, a methyl group, a phenyl group, a dimethylamino group, a diethylamino group, etc. In addition, when an asymmetric carbon is generated in these metallocene compounds, one of the stereoisomers or a mixture thereof (including a racemic mixture) is shown unless otherwise specified.
[0093] As a synthesis method for the metallocene complex represented by the general formula [a2], a conventionally known synthesis method can be appropriately selected and used. For example, the synthesis can be performed by referring to JP-T-2007-528925 and JP-A-2021-152155.
[0094] Component [B] is a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair. Component [B] may be used alone or in combination of two or more thereof. Component [B] is preferably a layered silicate. As the component [B], a conventionally known component can be appropriately selected and used. For specific examples of the component [B], reference can be made to paragraphs 0103 to 0111 of International Publication No. WO 2022 / 209773.
[0095] The component [C] used in the present invention is an organoaluminum compound, and a conventionally known one can be appropriately selected and used. For the component [C], reference can be made to paragraph 0112 of International Publication No. WO 2022 / 209773.
[0096] In addition, the preparation of the olefin polymerization catalyst preferably used in the present invention can be appropriately selected and used according to a conventionally known method, for example, by referring to paragraphs 0113 to 0116 of International Publication No. 2022 / 209773.
[0097] In addition, the polymerization method of the branched polypropylene resin (X) used in the present invention includes a method of homopolymerizing propylene or copolymerizing propylene and a comonomer in the presence of a propylene polymerization catalyst containing components [A-1], [A-2], [B] and [C]. As a specific polymerization method, a conventionally known method can be appropriately selected and used, and for example, paragraphs 0117 to 0123 of WO2022 / 209773 can be referred to.
[0098] The branched polypropylene resin (X) used in the present invention may be in the form of powder, particles, etc. Here, the particulate branched polypropylene resin (X) includes granulated products of the branched polypropylene resin (X).
[0099] When additives are mixed with the branched polypropylene resin (X), a Henschel mixer, a V blender, a ribbon blender, a kneader and / or a tumbler blender, etc. can be used. For the production of granules, a kneader such as a single screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer can be used.
[0100] 2. Linear polypropylene resin (Y) The linear polypropylene resin (Y) used in the present invention may be a homopolymer of propylene, or a copolymer of propylene and at least one selected from ethylene and α-olefins having 4 or more carbon atoms. The at least one comonomer selected from ethylene and an α-olefin having 4 or more carbon atoms may be ethylene and an α-olefin having 4 to 20 carbon atoms, for example, at least one comonomer selected from ethylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene. The branched polypropylene resin (Y) used in the present invention may be a propylene polymer consisting of propylene and 0 to 11 mol % of at least one selected from ethylene and α-olefins having 4 or more carbon atoms. The content of the comonomer may be more than 0 mol % or may be 0.5 mol % or more, with the upper limit being 7.5 mol % or less, in the total monomers. The linear polypropylene resin (Y) used in the present invention is preferably a copolymer of propylene and at least one selected from ethylene and α-olefins having 4 or more carbon atoms, from the viewpoint of suppressing an increase in the heat seal temperature of the film.
[0101] 2-1. Characteristics of linear polypropylene resin (Y) Characteristics (Y-1): The linear polypropylene resin (Y) used in the present invention has an MFR of 0.1 g / 10 min to 10 g / 10 min measured at a temperature of 230° C. and a load of 2.16 kg, from the viewpoints of processability in a casting method of the polypropylene resin composition and strength of the film. The MFR (230° C., load 2.16 kgf) of the linear polypropylene resin (Y) is preferably 0.1 g / 10 min to 8 g / 10 min, more preferably 0.1 g / 10 min to 6 g / 10 min.
[0102] The MFR of the linear polypropylene resin (Y) can be adjusted by changing the temperature conditions during propylene polymerization, changing the pressure conditions during propylene polymerization, and / or changing the method of adding a chain transfer agent such as hydrogen during polymerization.
[0103] Characteristics (Y-2): From the viewpoint of improving the transparency and productivity of the film, the linear polypropylene resin (Y) used in the present invention has an absolute molecular weight M abs The branching index g' (million) may be about 1, for example, 0.95 or more, or 0.97 or more. As mentioned above, the upper limit of g' is 1.00 by definition. A polypropylene resin having a g' (million) of about 1 indicates that the molecular shape is linear. g' (million) can be determined in the same manner as characteristic (X-4) above.
[0104] Characteristics (Y-3): The linear polypropylene resin (Y) used in the present invention has a Tm measured by DSC of preferably 110°C to 145°C, more preferably 120°C to 145°C, and even more preferably 120°C to 140°C, from the viewpoints of the heat sealing temperature and strength of the unstretched film. Tm can be determined in the same manner as for the above characteristic (X-2).
[0105] In order to obtain the Tm of the linear polypropylene resin (Y) used in the present invention, as in the above characteristic (X-2), a complex that optimizes the stereoregularity is selected, or a comonomer is used to control the degree of supercooling.
[0106] 2-2. Manufacturing method of linear polypropylene resin (Y) The polymerization catalyst for producing the linear polypropylene resin (Y) may be a Ziegler-Natta catalyst and / or a metallocene catalyst, but may also be another catalyst. Ziegler-Natta catalysts are described in Section 2.3.1 (pages 20-57) of "Polypropylene Handbook," edited by Edward P. Moore Jr., translated and supervised by Yasuda Tetsuo and Sakuma Nobuo, Kogyo Chosakai (1998). Ziegler-Natta catalysts include (1) titanium trichloride catalysts consisting of titanium trichloride and organoaluminum halide, magnesium chloride, titanium halide, (2) magnesium-supported catalysts consisting of solid catalyst components containing electron donor compounds, organoaluminum and organosilicon compounds, and (3) catalysts combining organoaluminum compound components with organosilicon-treated solid catalyst components formed by contacting solid catalyst components with organoaluminum and organosilicon compounds.
[0107] The metallocene catalyst includes a catalyst in combination with (i) a metallocene compound, (ii) a co-catalyst capable of being activated to a stable ionic state by reacting with the metallocene compound, and (iii) an organoaluminum compound. In order to improve the mechanical properties of the linear polypropylene resin (Y), the metallocene compound used to synthesize the linear polypropylene resin (Y) is preferably a crosslinked metallocene compound capable of stereoregular polymerization of propylene, and more preferably a crosslinked metallocene compound capable of isoregular polymerization of propylene.
[0108] Examples of the metallocene compound (i) include those described in JP-A-60-35007, JP-A-61-130314, JP-A-63-295607, JP-A-1-275609, JP-A-2-41303, JP-A-2-131488, JP-A-2-76887, JP-A-3-163088, JP-A-4-300887, JP-A-4-211694, JP-A-5-43616, JP-A-5-209013, JP-A-6-239914, JP-T-H7-504934 and JP-A-8-85708.
[0109] Specific examples of the metallocene compound (i) include: Methylenebis(2-methylindenyl)zirconium dichloride, Ethylenebis(2-methylindenyl)zirconium dichloride, Ethylene 1,2-(4-phenylindenyl)(2-methyl-4-phenyl-4H-azulenyl)zirconium dichloride, Isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(4-methylcyclopentadienyl)(3-t-butylindenyl)zirconium dichloride, Dimethylsilylene(2-methyl-4-t-butyl-cyclopentadienyl)(3'-t-butyl-5'-methyl-cyclopentadienyl)zirconium dichloride, Dimethylsilylenebis(indenyl)zirconium dichloride, Dimethylsilylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[4-(1-phenyl-3-methylindenyl)]zirconium dichloride, Dimethylsilylene(fluorenyl) t-butylamido zirconium dichloride, Methylphenylsilylenebis[1-(2-methyl-4-(1-naphthyl)-indenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4,5-benzoindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenyl-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-naphthyl-4H-azulenyl)]zirconium dichloride, Diphenylsilylenebis[1-(2-methyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(3-fluorobiphenylyl)-4H-azulenyl)]zirconium dichloride, Dimethylgermylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, and Dimethylgermylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride and the like zirconium compounds.
[0110] The metallocene compound (i) in which the zirconium is replaced with titanium or hafnium, and / or a mixture thereof, can also be used as a polymerization catalyst for producing a linear polypropylene resin (Y). The metallocene compound (i) in which the chloride is replaced with other halogen compounds, hydrocarbon groups such as methyl, isobutyl, and benzyl, amide groups such as dimethylamide and diethylamide, alkoxide groups such as methoxy and phenoxy, and hydride groups can also be used as a polymerization catalyst for producing a polypropylene resin (Y).
[0111] In order to improve the moldability of a resin composition containing a linear polypropylene-based resin (Y), the metallocene compound (i) which is a polymerization catalyst for producing the polypropylene-based resin (Y) is preferably a metallocene compound in which an indenyl group or an azulenyl group is crosslinked with a silicon or germyl group.
[0112] The polymerization catalyst for producing the linear polypropylene-based resin (Y) may be supported on an inorganic or organic compound. In order to improve the production amount of the polypropylene-based resin (Y), the support is preferably porous. The support is preferably an inorganic compound such as an ion-exchangeable layered silicate, zeolite, SiO2, Al2O3, silica alumina, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, or an organic compound such as a porous polyolefin, a styrene-divinylbenzene copolymer, or an olefin-acrylic acid copolymer, or a mixture thereof.
[0113] In order to improve the production amount of the linear polypropylene resin (Y), it is preferable to use a co-catalyst together with the metallocene compound. The co-catalyst is preferably an organoaluminum oxy-compound such as an aluminoxane compound, an ion-exchangeable layered silicate, a Lewis acid, a boron-containing compound, an ionic compound, or a fluorine-containing organic compound.
[0114] In order to improve the productivity of the linear polypropylene resin (Y), the organoaluminum compound (iii) is preferably a trialkylaluminum such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum or trioctylaluminum, a dialkylaluminum halide, an alkylaluminum sesquihalide, an alkylaluminum dihalide, diethylaluminum chloride, ethylaluminum chloride, diethylaluminum ethoxide, methylalumoxane, an alkylaluminum hydride or an organoaluminum alkoxide.
[0115] In order to improve the production efficiency of the polypropylene resin, the production method of the linear polypropylene resin (Y) is preferably a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. For the production of polypropylene and propylene random copolymers, a multi-stage polymerization method such as a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. can be used.
[0116] When additives are mixed with the linear polypropylene resin (Y), the linear polypropylene resin (Y) may be produced by mixing together with necessary additives using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender, etc. The linear polypropylene resin (Y) may be produced by kneading using a kneading machine such as a single screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer.
[0117] The linear polypropylene resin (Y) may be in the form of powder, particles, etc. The particles of the linear polypropylene resin (Y) include granulated products of the linear polypropylene resin (Y).
[0118] 3. Polypropylene resin composition The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing a branched polypropylene resin (X) and a linear polypropylene resin (Y) in a specific ratio described in detail below. From the viewpoint of strength of the non-stretched film, the polypropylene resin composition of the present invention contains a branched polypropylene resin (X) in an amount of 1% by mass to 99% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). The content of the branched polypropylene resin (X) may be 1% by mass or more, 10% by mass or more, 30% by mass or more, or 50% by mass or more, or may be 90% by mass or less, 80% by mass or less, or 70% by mass or less, relative to 100% by mass of the total mass of the resin (X) and the resin (Y). From the viewpoint of strength of the non-stretched film, the polypropylene resin composition of the present invention contains a linear polypropylene resin (Y) in an amount of 1% by mass to 99% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). The content of the linear polypropylene resin (Y) may be 10% by mass or more, 20% by mass or more, or 30% by mass or more, or may be 90% by mass or less, 70% by mass or less, or 50% by mass or less, relative to 100% by mass of the total mass of the resin (X) and the resin (Y).
[0119] The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing the branched polypropylene resin (X) and the linear polypropylene resin (Y) as essential components, and may further contain other components such as additives and other polymers different from the branched polypropylene resin (X) and the linear polypropylene resin (Y).
[0120] 3-1.Additives The polypropylene resin composition of the present invention may further contain additives as necessary in addition to the branched polypropylene resin (X) and linear polypropylene resin (Y). By appropriately selecting the additives, the functions of the polypropylene resin composition can be improved. The additives may be used alone or in combination of two or more. The additives include, for example, at least one selected from the group consisting of antioxidants, lubricants, antistatic agents, antiblocking agents, UV absorbers, light stabilizers, and neutralizing agents.
[0121] Examples of the antioxidant include phenol-based stabilizers such as 2,6-di-t-butyl-p-cresol, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane and n-octadecyl-3-(4'-hydroxy-3,5'-di-t-butylphenyl)propionate, and phosphite-based stabilizers such as bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite and tris(2,4-di-t-butylphenyl)phosphite. Examples of the lubricant include higher fatty acid amides and higher fatty acid esters. Examples of the antistatic agent include glycerin esters, sorbitan acid esters, and polyethylene glycol esters of fatty acids having 8 to 22 carbon atoms. Examples of anti-blocking agents include silica, calcium carbonate, and talc.
[0122] Furthermore, by incorporating an ultraviolet absorber and a light stabilizer in the polypropylene resin composition, the weather resistance of the polypropylene resin composition can be improved. Examples of the ultraviolet absorbent include compounds having an absorption band in the ultraviolet region, such as triazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, salicylate-based ultraviolet absorbents, cyanoacrylate-based ultraviolet absorbents, nickel chelate-based ultraviolet absorbents, inorganic fine particle-based ultraviolet absorbents, etc. Among these, triazole-based ultraviolet absorbents are a typical example. Examples of triazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-amylphenyl)benzotriazole, and 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole. Benzophenone-based ultraviolet absorbents include, for example, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, and the like. An example of the salicylate-based ultraviolet absorber is 4-t-butylphenyl salicylate. An example of a cyanoacrylate-based ultraviolet absorber is ethyl (3,3-diphenyl) cyanoacrylate. An example of the nickel chelate ultraviolet absorber is nickel dibutyldithiocarbamate. Examples of inorganic particulate ultraviolet absorbents include TiO2, ZnO2, and CeO2.
[0123] Typical light stabilizers include compounds having a hindered amine skeleton (hereinafter referred to as "HALS"). HALS includes sebacate type compounds, butanetetracarboxylate type compounds, succinic acid polyester type compounds, triazine type compounds, and the like. Examples of the sebacate type compound include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and the like. Examples of butane tetracarboxylate type compounds include tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, a condensate of 1,2,3,4-butane tetracarboxylic acid with 2,2,6,6-tetramethyl-4-piperidinol and tridecyl alcohol, and a condensate of 1,2,3,4-butane tetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and tridecyl alcohol. An example of the succinic acid polyester type compound is a condensation polymer of succinic acid and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine. Examples of triazine-type compounds include N,N'-bis(3-aminopropyl)ethylenediamine·2,4-bis{N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino}-6-chloro-1,3,5-triazine condensate, poly{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino, and poly(6-morpholino-s-triazine-2,4-diyl){(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino.
[0124] In the polypropylene resin composition of the present invention, the total content of the additives is not particularly limited as long as it is appropriately selected according to the properties of the additives. In the polypropylene resin composition of the present invention, the upper limit of the total content of the additives may be, for example, 10 parts by mass or less, 1 part by mass or less, or 0.5 parts by mass or less, and the lower limit may be 0 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the linear polypropylene resin (Y).
[0125] 3-2.Other polymers The polypropylene resin composition of the present invention may further contain other polymers as necessary in addition to the above-mentioned branched polypropylene resin (X) and linear polypropylene resin (Y). The other polymers can improve the performance or adjust the properties of the branched polypropylene resin composition as modifiers in the polypropylene resin composition. Examples of the other polymers used as modifiers include, but are not limited to, elastomers, polyethylene resins, etc. Examples of the elastomer include ethylene-α-olefin copolymers, binary random copolymer resins of propylene and an α-olefin having 4 to 12 carbon atoms, and ternary random copolymer resins of propylene, ethylene, and an α-olefin having 4 to 12 carbon atoms. Examples of styrene-based elastomers include hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-vinylated polyisoprene block copolymers, and hydrogenated styrene-butadiene random copolymers.
[0126] Examples of polyethylene resins include ethylene / α-olefin copolymers such as low-density polyethylene and linear low-density polyethylene, and their density is 0.860 g / cm. 3 ~0.910g / cm 3 and preferably in the range of 0.870 g / cm 3 ~0.905g / cm 3 More preferably, it is 0.875 g / cm 3 ~0.895g / cm 3 If the content exceeds the above range, the transparency may decrease. The density is a value measured at 23° C. in accordance with JIS K7112. The α-olefin used in the ethylene / α-olefin copolymer is preferably an α-olefin having 3 to 18 carbon atoms. Specific examples include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, 4,4-dimethylpentene-1, etc. The α-olefin may be one type or a combination of two or more types. Examples of such ethylene / α-olefin copolymers include ethylene-based elastomers, ethylene-propylene-based rubbers, etc. In particular, ethylene / α-olefin copolymers called metallocene-based polyethylenes, which are produced using metallocene-based catalysts with little loss of transparency, are preferred.
[0127] In the polypropylene resin composition of the present invention, the total content of the other polymers is not particularly limited as long as the effect is not impaired and may be appropriately selected according to the purpose. The upper limit of the total content of the other polymers may be, for example, 50 parts by mass or less, 30 parts by mass or less, or 10 parts by mass or less, and the lower limit may be 0 parts by mass, but may be 1 part by mass or more, or 3 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the linear polypropylene resin (Y).
[0128] The polypropylene resin composition of the present invention contains 100 parts by mass of the branched polypropylene resin (X) and the linear polypropylene resin (Y) in total, or other components that do not impair the effects of the present invention, as necessary. Examples of the method for mixing these components include mixing with a Henschel mixer, V blender, ribbon blender, tumbler blender, etc., and melt-kneading with a kneader such as a single-screw extruder, multi-screw extruder, kneader, or Banbury mixer, as necessary. There are no particular limitations on the mixing method, as long as the effects of the present invention are not impaired in either case.
[0129] 4. Characteristics of polypropylene resin composition The polypropylene resin composition of the present invention may have an MFR of 1 g / 10 min to 50 g / 10 min, 2 g / 10 min to 30 g / 10 min, or 3 g / 10 min to 15 g / 10 min, measured at a temperature of 230° C. under a load of 2.16 kg, from the standpoints of processability in a casting method of the polypropylene resin composition and transparency and strength of the film.
[0130] In the polypropylene resin composition of the present invention, the Tm measured by DSC is preferably 110°C to 145°C, more preferably 120°C to 145°C, and even more preferably 120°C to 140°C, from the viewpoints of the heat sealing temperature and strength of the unstretched film. In the polypropylene resin composition of the present invention, Tc measured by DSC is preferably 60°C to 140°C, more preferably 70°C to 120°C, and even more preferably 80°C to 110°C, in terms of the heat sealing temperature and strength of the unstretched film.
[0131] From the viewpoint of increasing strength, the polypropylene resin composition of the present invention may have a melt tension (MT) at 230° C. of 0.1 g to 5 g, or may be 0.3 g to 4 g.
[0132] 5. Uses of polypropylene resin compositions The polypropylene resin composition of the present invention can be used for producing various molded articles by appropriately molding into a desired shape by means of pressure molding, film molding, vacuum molding, extrusion molding, extrusion lamination molding, foam molding, blow molding, injection molding, or the like. The polypropylene resin composition of the present invention can be suitably used for non-stretched films, in particular. That is, one aspect of the polypropylene resin composition of the present invention is a branched polypropylene resin composition for non-stretched films.
[0133] 6. Method for producing polypropylene resin composition The polypropylene resin composition of the present invention can be produced by blending, mixing, and melt-kneading the branched polypropylene resin (X), the linear polypropylene resin (Y), and additives used as necessary in the above-mentioned content ratios by a conventionally known method.
[0134] The polypropylene resin composition of the present invention can be mixed by dry blending using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender or the like. In addition, when producing the composition by melt-kneading and granulation, the above-mentioned mixture of components may be kneaded at the same time. Furthermore, in order to improve the performance, each component may be divided and kneaded separately, that is, for example, a method may be adopted in which a part of the components to be used is first kneaded, and then the remaining components are kneaded and granulated.
[0135] The polypropylene resin composition of the present invention is preferably produced by dry blending the components to be used. A preferred embodiment of the method for producing a polypropylene-based resin composition of the present invention is a method for producing a polypropylene-based resin composition, comprising a step of dry-blending a branched polypropylene-based resin (X) having the above-mentioned properties (X-1) to (X-3) and a linear polypropylene-based resin (Y) having the above-mentioned property (Y-1). By mixing the branched polypropylene resin (X) and the linear polypropylene resin (Y) by dry blending, it is possible to uniformly mix them in a relatively short time at low cost, and stable performance can be obtained. The resulting mixture is usually melt-kneaded as described above.
[0136] II. Film The film of the present invention is a film containing the polypropylene resin composition of the present invention. The film of the present invention is produced using the polypropylene-based resin composition of the present invention, and may be a polypropylene-based resin film. The film of the present invention may be produced by a film-forming step using the polypropylene resin composition of the present invention by a cast film-forming method, or may be a non-stretched film. The film of the present invention may be a single-layer film, or may be a multi-layer film containing at least one layer made of the polypropylene resin composition of the present invention. The film of the present invention can be used for packaging food such as bread and vegetables, packaging clothing such as shirts, packaging industrial parts, etc. The film can also be used as a substrate for films laminated to films such as cellophane, paper, textiles, paperboard, aluminum foil, polyamide resins such as nylon 6 and nylon 66, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, and oriented polypropylene by lamination methods such as dry lamination and sand lamination.
[0137] The production of a non-oriented film by the cast film production method is preferably carried out by melting the polypropylene resin composition of the present invention using an extruder equipped with a T-die to form a sheet, extruding the sheet, blowing air supplied from a blower or the like onto the sheet to bring it into close contact with a chill roll, cooling and solidifying the sheet, and then taking it up with a take-up machine.
[0138] The die diameter is typically φ50 mm to φ500 mm, and the die lip width is typically 0.8 mm to 4.0 mm. From the viewpoints of design such as film transparency and productivity such as stable continuous film production, the film production temperature is preferably 170°C to 250°C, and more preferably 170°C to 230°C. In order to improve the uniformity of the film, such as by suppressing fluttering of the film, the forming speed is preferably 5 m / min to 300 m / min, and more preferably 10 m / min to 250 m / min.
[0139] The thickness of the formed film is not particularly limited and may be appropriately selected depending on the application. The thickness of the film is usually 1 μm to 250 μm, may be 3 μm to 200 μm, or may be 5 μm to 150 μm.
[0140] The film of the present invention is also excellent in strength. The Young's modulus, which is an index of film strength, indicates that the greater the value, the higher the strength. The film of the present invention has an average value of the Young's modulus in the direction horizontal to the film-forming direction (MD) and in the direction perpendicular to the film-forming direction (TD), "Young's modulus (average)," of preferably 500 MPa or more, more preferably 800 MPa or more. In the present invention, Young's modulus is measured in accordance with JIS K7127: 1999. The higher the Young's modulus value, the higher the strength.
[0141] The film of the present invention is also excellent in tearability. The smaller the tear strength, which is an index of the tearability of a film, the better the tearability. The film of the present invention has a tear strength of preferably 7 N / mm or less, more preferably 2 N / mm or less, both in the direction horizontal to the film-forming direction (MD) and in the direction perpendicular to the film-forming direction (TD). In the present invention, the tear strength is measured by the Elmendorf tear method in accordance with JIS K7128-2:1998.
[0142] In the film of the present invention, it is preferable that Tm (° C.) and the Young's modulus (average) (MPa) satisfy the relationship represented by the following formula (7). Young's modulus (average)>11.5×(Tm)-942 Equation (7) The relationship between Tm and Young's modulus (average) defined by the above formula (7) can be used as an index of the strength of the film corresponding to Tm. Satisfying the above formula (7) indicates that the film of the present invention has excellent film strength corresponding to Tm. That is, in order to distinguish the film of the present invention from the conventional one, the Young's modulus (average) is considered to be a function positively correlated with an increase in Tm, the parameters of the function are set, and it is shown that the Young's modulus of the film of the present invention is larger than that of the conventional film in proportion to Tm. Specifically, based on the data of the examples and comparative examples having the same level of fluidity and Tm as the examples, the values of Tm and Young's modulus that distinguish the examples from the comparative examples of the conventional technology are assumed, and the parameters of the relational equation that holds between the Tm and Young's modulus are determined by the least squares method (see FIG. 6). EXAMPLES
[0143] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following examples, the autoclave was thoroughly dried in advance by passing nitrogen through it under heating before use, and the catalyst preparation and polymerization were all carried out under an inert gas. In the present embodiment, the term "MD" refers to the direction in which the film is fed during extrusion molding, and the term "TD" refers to the direction perpendicular to the direction in which the film is fed during extrusion molding and parallel to the film surface.
[0144] I. Measurement and Evaluation Methods The following (1) to (15) were measured and calculated by the methods described in this specification. (1) MFR (The measured MFR value was used to calculate the values on the right side of the above formulas (1), (4) and (6).) (2) Ea in dynamic viscoelasticity measurement (3) Tm and Tc measured by DSC (The measured Tm value was used to calculate the value on the right side of the above formula (7).) (4) Mw / Mn and Mz / Mw obtained by GPC (5) W1 million, W2 million, and W2 million / W1 million in the integral molecular weight distribution curve obtained by GPC (6) g' (million), g' (Mw abs ), and [g'(Mw abs )-g'(1 million)] (7) 13 Ethylene content measured by C-NMR (8) 13 mm, [2,1 bond] amount, and [1,3 bond] amount measured by C-NMR (9) 13 LCB number measured by C-NMR (10) SHI@1.0s obtained from extensional viscosity measurement -1 and MBI (11) M.T. (12) MaxDraw (13)[Vi], Rv, number of LCBs / ([Vi]+number of LCBs) (14)Young’s modulus The Young's modulus of the film in the MD direction is called "Young's modulus (MD)" and the Young's modulus of the film in the TD direction is called "Young's modulus (TD)." The average value of Young's modulus (MD) and Young's modulus (TD) is called "Young's modulus (average)." (15) Tear strength The tear strength of the film in the MD direction is referred to as "tear strength (MD)" and the tear strength of the film in the TD direction is referred to as "tear strength (TD)".
[0145] II. Production of polypropylene resin composition and film 1. Branched polypropylene resin (X) 1-1. Production of branched polypropylene resin (X1) (1) Synthesis of catalyst component (A) (1-1) Synthesis Example 1: Synthesis of catalyst component [A-1] (Complex 1) Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium: rac-Dichloro[1,1′-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium was synthesized according to the method of Synthesis Example 1 in JP2012-149160A.
[0146] (1-2) Synthesis Example 2: Synthesis of catalyst component [A-2] (Complex 2) 1) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2): (1-a) Synthesis of 2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene: The synthesis was carried out with reference to the method described in Example 1 of JP-A-2003-517010. (1-b) Synthesis of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane: 2,5-Dimethyl-3-phenyl-hydrocyclopenta[b]thiophene (8.8g, 39mmol) and THF (200ml) were added to a 500ml glass reaction vessel and cooled to -70℃. n-Butyllithium-n-hexane solution (1.55mol / L, 25ml, 39mmol) was added dropwise. After the addition, the mixture was stirred for 2 hours while gradually returning to room temperature. The mixture was cooled again to -70℃, 1-methylimidazole (0.15ml, 1.9mmol) was added, and a THF solution (30ml) containing dimethyldichlorosilane (2.5g, 19mmol) was added dropwise. After the addition, the mixture was stirred overnight while gradually returning to room temperature. Distilled water was added to the reaction solution obtained, which was then transferred to a separatory funnel and washed with saline until neutral. Sodium sulfate was added and the reaction solution was left overnight to dry. The sodium sulfate was filtered off, the solvent was removed under reduced pressure, and the resulting solid was purified using a silica gel column to obtain a white powder of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (9.8 g, 99% yield). (1-c) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex A): Dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (6.1g, 12mmol) and 200ml of diethyl ether were added to a 500ml glass reaction vessel, and the vessel was cooled to -70℃ in a dry ice-methanol bath. A n-butyllithium-n-hexane solution (1.55mol / L, 16ml, 24mmol) was added dropwise to the vessel. After the addition, the mixture was returned to room temperature and stirred for 2 hours. The solvent of the reaction solution obtained was concentrated under reduced pressure to about 20ml, after which 250ml of toluene and 10ml of THF were added, and the mixture was cooled to -70℃ in a dry ice-methanol bath. 3.8g (12mmol) of hafnium tetrachloride was added to the vessel. The mixture was then gradually returned to room temperature and stirred overnight. The solvent was distilled off under reduced pressure and the resulting solid was recrystallized from toluene / hexane to obtain 0.87 g (yield 10%) of racemic dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (purity 97%) as yellow crystals.
[0147] The racemic mixture was analyzed by proton nuclear magnetic resonance ( 1 The identified values by H-NMR are shown below. 1 H-NMR (CDCl3) Identification Results Racemic: δ1.06(s,6H), δ2.42(s,6H), δ2.59(s,6H), δ8.51(s,2H), δ7.28~δ7.33(m,2H), δ7.39~δ7.43(m,4H), δ7.46~δ7.50(m,4H)
[0148] (2) Synthesis example of component (B): Chemical treatment of ion-exchangeable layered silicate Into a 1 L three-neck flask equipped with a stirring blade and a reflux device, 645.1 g of distilled water and 82.6 g of 98% sulfuric acid were added and heated to 95°C. 100 g of commercially available montmorillonite (Benclay KK manufactured by Mizusawa Chemical Industry Co., Ltd., Al=9.78% by mass, Si=31.79% by mass, Mg=3.18% by mass, Al / Si (molar ratio)=0.320, average particle size 14 μm) was added thereto, and the mixture was reacted for 320 minutes at 95° C. After 320 minutes, 0.5 L of distilled water was added to stop the reaction, and 255 g of a cake-like solid was obtained by filtration. This cake (1 g) contained 0.31 g of the chemically treated montmorillonite (intermediate). The chemical composition of the chemically treated montmorillonite (intermediate) was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, and Al / Si (molar ratio) = 0.222. 1545g of distilled water was added to the cake to make a slurry, and the temperature was raised to 40℃. 5.734g of lithium hydroxide hydrate was added as a solid to the slurry, and the reaction was carried out at 40℃ for 1 hour. After 1 hour, the reaction slurry was filtered and washed three times with 1L of distilled water, and a cake-like solid was obtained again. The cake-like solid obtained was pre-dried overnight at 90°C or higher under normal pressure, and then dried under reduced pressure for 2 hours or more after the bumping subsided using an oil bath at 200°C to obtain 80 g of chemically treated montmorillonite. The chemical composition of this chemically treated montmorillonite was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, Al / Si (molar ratio) = 0.222, Li = 0.53 mass%.
[0149] (3) Preparation of catalyst 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (45 μmol) prepared in the synthesis example of the catalyst component [A-2] was dissolved in toluene (9 mL) to prepare solution 2.
[0150] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above-mentioned solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Thereafter, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was further added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 28.2 g of a prepolymerized catalyst (Catalyst 1). The prepolymerization ratio (value obtained by dividing the amount of prepolymerized polymer by the amount of solid catalyst) was 1.82.
[0151] (4) Polymerization The 20 L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7 mL of a heptane solution of triisobutylaluminum (140 mg / mL), 321 g of ethylene, 0.68 NL of hydrogen, and 5000 g of liquid propylene were introduced into the polymerization tank, and the temperature was raised to 63°C. Then, 60 mg of the above catalyst 1 (excluding the prepolymerized polymer) was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature inside the tank was quickly raised to 65°C. The temperature was kept at 65°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1852 g of a branched polypropylene resin (X1) was obtained. The obtained resin was used for GPC, 3D-GPC, 13 C-NMR and DSC were measured.
[0152] (5) Production of branched polypropylene resin pellets (X1) (granulation) 100 parts by mass of the obtained branched polypropylene resin (X1) was mixed with 0.125 parts by mass of a phenolic antioxidant IRGANOX1010 (manufactured by BASF Japan, tetrakis [methylene-3- (3', 5'-di-t-butyl-4'-hydroxyphenyl) propionate] methane) and 0.125 parts by mass of a phosphite antioxidant IRGAFOS168 (manufactured by BASF Japan, tris (2, 4-di-t-butylphenyl) phosphite) and mixed for 3 minutes at room temperature using a high-speed stirring mixer (Henschel mixer, manufactured by Nippon Coke & Co., Ltd.). Then, using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.), the screw rotation speed was 400 rpm and the kneading temperature was 80, 120, and 230 ° C. from the bottom of the hopper (the same temperature from then until the die outlet). The molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter. The MFR of the obtained pellets was 7.8g / 10min. Using the obtained pellets, Ea, MT, extensional viscosity, TREF, and MaxDraw were measured. The evaluation results of each property are shown in Table 1.
[0153] 1-2. Production of branched polypropylene resin (X2) Polymerization was carried out in the same manner as in Example 1 for producing a branched polypropylene resin (X1), except that 400 mg of catalyst 1 (mass excluding the prepolymerized polymer), 138 g of ethylene, and 0.34 NL of hydrogen were introduced, the temperature inside the vessel was raised to 70° C., and the temperature was maintained at 70° C. As a result, 2226 g of a branched polypropylene resin (X2) was obtained. The obtained branched polypropylene resin (X2) was pelletized in the same manner as in the production of the branched polypropylene resin pellets (X1), and the MFR of the obtained pellets was 3.0 g / 10 min. The results of the evaluation of each property are shown in Table 1.
[0154] [Reference: Production of branched polypropylene resin] <Reference: Production of branched polypropylene resin (CX1)> (1) Preparation of catalyst (1-1) Synthesis of catalyst component [CA-2] Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium: rac-Dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) was synthesized according to the method of Example 7 of JP-A-11-240909.
[0155] (1-2) Synthesis example of catalyst 2 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (45 μmol) prepared in the synthesis example of the comparative catalyst component [CA-2] was dissolved in toluene (9 mL) to prepare solution 2.
[0156] Triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added to a 1 L flask containing the above-mentioned chemically treated montmorillonite, and then the above solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Then, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining the temperature at 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 30.9% prepolymerized catalyst (catalyst 2). The prepolymerization rate was 2.09%.
[0157] (2) Polymerization and granulation The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL), 0.68NL of hydrogen, and 5000g of liquid propylene were introduced into the polymerization tank, and the temperature was raised to 63°C. Then, 310mg of the catalyst 2, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature inside the tank was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 2288g of propylene homopolymer was obtained. The polymer thus obtained was pelletized in the same manner as in the production of pellets of the branched polypropylene resin (X1), and the MFR of the pellets thus obtained was 3.3 g / 10 min. The results of the evaluation of each property are shown in Table 1.
[0158] <Reference: Production of branched polypropylene resin (CX2)> Polymerization was carried out in the same manner as in the polymerization for producing the reference branched polypropylene resin (CX1), except that 230 mg of catalyst 2 (excluding the prepolymerized polymer) and 1.02 NL of hydrogen were introduced. As a result, 1978 g of a polymer was obtained. The polymer thus obtained was pelletized in the same manner as in the production of pellets of the branched polypropylene resin (X1), and the MFR of the pellets thus obtained was 9.9 g / 10 min. The results of evaluation of each property are shown in Table 1.
[0159] <Reference: Production of branched polypropylene resin (CX3)> Polymerization was carried out in the same manner as in the polymerization for producing the reference branched polypropylene resin (CX1), except that the catalyst 2 was used in an amount of 220 mg (excluding the prepolymerized polymer) and 1.11 NL of hydrogen was introduced. As a result, 1936 g of a polymer was obtained. The obtained polymer was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the obtained pellets was 15.0 g / 10 min. The results of evaluation of each property are shown in Table 1.
[0160] [Table 1]
[0161] FIG. 1 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for the branched polypropylene resins (X1) to (X2) used in each example and the reference branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 3 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for the branched polypropylene resins (X1) to (X2) used in each example and the reference branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum winding speed (MaxDraw) at 230° C., and data for the branched polypropylene resins (X1) to (X2) used in each example and the reference branched polypropylene resins (CX1) to (CX3) are plotted.
[0162] 2. Linear polypropylene resin (Y) As the linear polypropylene resin (Y), the following polypropylene resins (Y1) to (Y2) were prepared. Polypropylene resin (Y1): Made by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) FX4GF", MFR = 7 g / 10 min, Tm = 125°C, g' (million) = 1.00 Polypropylene resin (Y2): Made by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) FW4BA", MFR = 7 g / 10 min, Tm = 138°C, g' (million) = 1.00
[0163] 3. Production of polypropylene resin composition and film production [Examples 1 to 5 and Comparative Examples 1 to 2] (1) Production of polypropylene resin composition Any one of pellets (X1) to (X2) of branched polypropylene resin (X) and pellets (Y1) to (Y2) of linear polypropylene resin (Y) in the amounts shown in Table 2 were put into a high-speed stirring mixer and stirred for 3 minutes to obtain mixed pellets. The amounts shown in Table 2 are shown in mass % relative to the total mass of the resin (X) and the resin (Y), which is 100 mass %. Regarding the pellets used for measuring MFR and Tm of the polypropylene resin composition, the mixed pellets were further melt-kneaded using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.) at a screw rotation speed of 400 rpm and kneading temperatures of 80, 120 and 230°C (the same temperature from the bottom of the hopper to the die outlet), and the molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter.
[0164] (2) Manufacturing of non-oriented films The mixed pellets of the polypropylene resin composition obtained above were put into the extruder of a film molding machine, extruded at an extruder temperature of 220°C and a die temperature of 230°C, and then the molten resin was brought into contact with a cooling roll adjusted to 30°C to solidify, while adjusting the discharge amount and take-up speed so that the film width was 300 mm and the thickness was 30 μm. The polypropylene resin composition was extruded under conditions of a total discharge amount of 5 kg / hour, and a non-stretched cast film was produced under conditions of a take-up speed of 20 m / min. The physical properties of the obtained non-stretched cast film are shown in Table 2.
[0165] [Table 2]
[0166] FIG. 6 is a graph in which the horizontal axis represents Tm (°C) and the vertical axis represents Young's modulus (average) (MPa), and data (Young's modulus (average) versus Tm) of the polypropylene-based resin films shown in the examples and comparative examples are plotted. From Examples 1 to 5 and Comparative Examples 1 and 2, it was shown that the polypropylene resin composition of the present invention, which contains the branched polypropylene resin (X), can be molded into a non-oriented film having high strength commensurate with Tm and excellent tearability.
[0167] The performance evaluation for preparing a catalyst for producing the branched polypropylene resin (X) of the present invention is shown below. [Reference Example 1]: Performance evaluation of complex 1 as catalyst component (A) (Preparation of Catalyst R1) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (65 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 35 mL of heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (0.15 mmol) synthesized in Synthesis Example 1 was dissolved in toluene (30 mL) to prepare a solution.
[0168] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 40 minutes to obtain 29.5 g of a prepolymerized catalyst (Catalyst R1). The prepolymerization rate was 1.95.
[0169] (polymerization) The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) and 0.51NL of hydrogen were introduced into the polymerization tank, followed by 5000g of liquid propylene, and the temperature was raised to 63°C. Then, 300mg of the catalyst R1, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1740g of propylene homopolymer was obtained. Table 2 shows the results of MFR, GPC, and NMR measurements using the obtained polymer.
[0170] [Reference Example 2]: Performance evaluation of complex 2 as catalyst component (A) (Preparation of Catalyst R2) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (0.15 mmol) synthesized in Synthesis Example 2 was dissolved in toluene (30 mL) to prepare a solution.
[0171] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 32.0 g of a prepolymerized catalyst (Catalyst R2). The prepolymerization rate was 2.20.
[0172] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R2 was used instead of catalyst R1, 100 mg of the mass excluding the prepolymerized polymer, and 1.19 NL of hydrogen was introduced. As a result, 1153 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 2.
[0173] [Reference Example 3]: Performance evaluation of complex 3 as catalyst component (A) (Preparation of catalyst R3) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (0.15 mmol) synthesized in Synthesis Example 3 was dissolved in toluene (30 mL) to prepare a solution.
[0174] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 31.0 g of a prepolymerized catalyst (Catalyst R3). The prepolymerization rate was 2.10.
[0175] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R3 was used instead of catalyst R1, 300 mg of the mass excluding the prepolymerized polymer, and 0.51 NL of hydrogen was introduced. As a result, 1570 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 3.
[0176] From the results of Reference Examples 1 to 3 in Table 3, it was shown that complex 1 can be used as a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is performed using component [A-1] at 70°C, and complex 2 can be used as a metallocene compound that gives a propylene homopolymer a-2 having a number average molecular weight (Mn) larger than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and smaller than 0.5 when propylene homopolymerization is performed using component [A-2] at 70°C, and the propylene homopolymer a-2 can be used as a metallocene compound in which the ratio of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is larger than that of the propylene homopolymer a-1. Complex 3 was a metallocene compound that gave a propylene homopolymer having a larger Mn than the propylene homopolymer a-1 but an Rv of 0 when propylene homopolymer was subjected to propylene homopolymerization at 70°C.
[0177] [Table 3]
Claims
1. A polypropylene resin composition comprising a branched polypropylene resin (X) having the following properties (X-1) to (X-3) and a linear polypropylene resin (Y) having the following property (Y-1), the resin (X) being present in an amount of 1% by mass to 99% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 155.0°C. Property (X-3): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): MFR measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 10 g / 10 min.
2. The polypropylene resin composition according to claim 1, wherein the linear polypropylene resin (Y) is a copolymer of propylene with at least one selected from the group consisting of ethylene and α-olefins having 4 or more carbon atoms.
3. The present invention relates to a method for producing a polypropylene-based resin composition, the method comprising the step of dry-blending a branched polypropylene-based resin (X) having the following properties (X-1) to (X-3) and a linear polypropylene-based resin (Y) having the following property (Y-1). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The melting point (Tm) measured by differential scanning calorimetry (DSC) is less than 155.0°C. Property (X-3): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): MFR measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 10 g / 10 min.
4. A film comprising the polypropylene resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Crystalline synthetic resin composition
JP1996003364A
Crystalline synthetic resin composition
JP1997118776A
Polypropylenic resin composition
JP2008127487A
Polypropylene unstretched film
JP2011236357A
Polypropylene-based resin composition for high rigidity film
JP2016011380A
Cited By
Foaming resin compositions, insulated wires, and transmission cables
JP7866696B1